Separator, and electrochemical device and electronic device comprising same

By using porous coating in the separator of lithium-ion batteries, the problem of reducing the storage space of the electrolyte is solved, the circulation performance and thermal safety performance of the electrochemical device are improved, and the problems of rising liquid and interfacial purple spot lithium are improved.

CN119864601APending Publication Date: 2025-04-22DONGGUAN AMPEREX TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510065460.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In lithium-ion batteries, due to the increase in compaction density of the electrode sheet and the thinning of the separator thickness, the storage space of the electrolyte is reduced, which in turn causes problems such as the decrease in the liquid retention volume of the electrolyte, the purple spots on the interface and the circulating dive.

Method used

A separator is used, which includes a porous substrate and a porous coating, which consists of the first filler particles, the second microsphere filler particles, the third polymer binder microsphere particles and the binder. The second microsphere filler particles and the third polymer binder microsphere particles have a hollow structure and a plurality of porous structures, which improves the porosity of the porous coating and the electrolyte storage space.

Benefits of technology

It improves the heat resistance and adhesion of the diaphragm, enhances the circulation and thermal safety performance of the electrochemical device, and improves the problem of rising liquid and the problem of lithium-ion spots on the interface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005244511090000291
    Figure BDA0005244511090000291
  • Figure BDA0005244511090000321
    Figure BDA0005244511090000321
  • Figure BDA0005244511090000331
    Figure BDA0005244511090000331
Patent Text Reader

Abstract

The invention discloses a diaphragm, and an electrochemical device and an electronic device comprising the same, the diaphragm comprises a porous base material and a porous coating arranged on at least one side of the porous base material, the porous coating comprises first filler particles, second microsphere filler particles, third polymer binder microsphere particles and a binder; each second microsphere filler particle comprises a cavity and a shell covering the cavity, the shell of each second microsphere filler particle comprises a plurality of pore structures, and the average particle size of the second microsphere filler particles is 0.2-2 microns; each third polymer binder microsphere particle comprises a cavity and a shell covering the cavity, the shell of each third polymer binder microsphere particle comprises a plurality of pore structures, and the average particle size of each third polymer binder microsphere particle is 1.5-10 [mu] m. The electrochemical device has both good cycle performance and thermal safety performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of electrochemical technology, and specifically relates to a diaphragm, and an electrochemical device and an electronic device containing the diaphragm. Background Art

[0002] As the demand for high energy density of lithium-ion batteries continues to increase, the compaction density of electrode plates continues to increase, and the thickness of the diaphragm continues to decrease, resulting in a reduction in the internal electrolyte storage space of lithium-ion batteries and a reduction in the amount of electrolyte retained. During the use of lithium-ion batteries, as the cycle of charge and discharge progresses, the amount of electrolyte retained gradually decreases, and purple spots and lithium precipitation are prone to occur at the interface of the electrode plates, and even lead to cycle diving. If the problem of reduced electrolyte retention is improved by increasing the amount of electrolyte injection, lithium-ion batteries, especially soft-pack lithium-ion batteries, are prone to swelling after packaging, which will also affect the use of lithium-ion batteries. Summary of the invention

[0003] The present application provides a diaphragm, and an electrochemical device and an electronic device comprising the diaphragm, wherein the electrochemical device has both good cycle performance and thermal safety performance.

[0004] In the first aspect, the present application provides a diaphragm, comprising a porous substrate and a porous coating disposed on at least one side of the porous substrate, wherein the porous coating comprises first filler particles, second microsphere filler particles, third polymer binder microsphere particles and a binder; the second microsphere filler particles comprise a cavity and a shell covering the cavity, the shell of the second microsphere filler particles comprises a plurality of pore structures, and the average particle size of the second microsphere filler particles is 0.2 μm to 2 μm; the third polymer binder microsphere particles comprise a cavity and a shell covering the cavity, the shell of the third polymer binder microsphere particles comprises a plurality of pore structures, and the average particle size of the third polymer binder microsphere particles is 1.5 μm to 10 μm. The first filler particles do not have a hollow structure.

[0005] The porous coating of the diaphragm of the present application includes second microsphere filler particles and third polymer binder microsphere particles. The second microsphere filler particles and the third polymer binder microsphere particles are hollow structures and the shell includes multiple pore structures. The pore structure connects the outside and the cavity, thereby increasing the porosity of the porous coating and making the porous coating and the diaphragm have lower ionic impedance; in addition, after liquid injection, the electrolyte can enter the cavity through the pore structure of the shell, thereby increasing the electrolyte storage space of the porous coating, allowing more electrolyte to be stored in the diaphragm, and improving the liquid swelling problem; in addition, during the cyclic charge and discharge process of the electrochemical device, especially in the late cycle, the electrolyte stored in the cavity can also be released through the pore structure of the shell, thereby reducing the problem of interfacial purple spot lithium precipitation caused by electrolyte shortage and improving the cycle performance of the electrochemical device using the diaphragm. By making the average particle size of the second microsphere filler particles 0.2μm to 2μm, the porous coating can have a higher packing density, thereby improving the heat resistance of the diaphragm, improving the thermal safety performance of the electrochemical device, and making the porous coating have more pores, thereby improving the ion transport characteristics of the diaphragm and improving the cycle performance of the electrochemical device. By making the average particle size of the third polymer binder microsphere particles 1.5μm to 10μm, the diaphragm can be bonded to the electrode plate, thereby improving the thickness consistency of the electrochemical device, and further forming a certain gap (also known as Gap) between the diaphragm and the electrode plate, which can buffer the volume expansion of the electrode plate, improve the interface electrolyte wettability at the corner, improve the problem of purple spot lithium precipitation at the corner interface, improve the cycle performance of the electrochemical device, and also make the electrochemical device have a higher energy density. The porous coating of the diaphragm of the present application also includes a first filler particle, which can improve the heat resistance of the diaphragm. Therefore, the diaphragm provided in the embodiment of the present application has high heat resistance, high adhesion, good electrolyte wettability and good electrolyte liquid retention. When used in electrochemical devices, it can improve the problem of liquid swelling and the problem of purple spot lithium precipitation on the interface, so that the electrochemical device can have both good cycle performance and thermal safety performance.

[0006] In some embodiments, the average particle size of the second microsphere filler particles is 0.3 μm to 2 μm. The second microsphere filler particles meeting this range are more conducive to improving the cycle performance and energy density of the electrochemical device.

[0007] In some embodiments, the average particle size of the third polymer binder microsphere particles is 3 μm to 8 μm. The third polymer binder microsphere particles meeting this range are more conducive to improving the cycle performance and energy density of the electrochemical device.

[0008] In some embodiments, the third polymeric binder microsphere particles have an average particle size greater than an average particle size of the second microsphere filler particles.

[0009] By making the average particle size of the third polymer binder microsphere particles larger than the average particle size of the second microsphere filler particles, the diaphragm and the electrode plates can be better bonded, and a sufficient gap can be formed between the diaphragm and the electrode plates to buffer the volume expansion of the electrode plates, thereby better improving the electrolyte wettability at the corner interface and improving the problem of purple spot lithium precipitation at the corner interface.

[0010] In some embodiments, the average particle size of the first filler particles is 0.2 μm to 2 μm, and can be 0.3 μm to 1 μm. This can make the electrochemical device have a higher energy density, and the porous coating have a higher packing density, thereby improving the heat resistance of the diaphragm and the thermal safety performance of the electrochemical device, and can also make the porous coating have more pores, thereby improving the ion transport characteristics of the diaphragm and the cycle performance of the electrochemical device.

[0011] In some embodiments, the third polymer binder microsphere particles are embedded in the pores formed by the accumulation of the first filler particles and the second microsphere filler particles and form protrusions on the surface of the porous coating, thereby achieving a better bonding effect. In addition, a certain gap can be formed between the diaphragm and the electrode plate. The gap can buffer the volume expansion of the electrode plate, improve the interfacial electrolyte wettability at the corners, enhance the ion transport characteristics of the diaphragm, and enhance the cycle performance of the electrochemical device.

[0012] In some embodiments, the porous coating includes a heat-resistant layer and an adhesive layer, the heat-resistant layer is arranged on at least one side of the porous substrate, the adhesive layer is arranged on at least a portion of the surface of the heat-resistant layer, the heat-resistant layer includes first filler particles, second microsphere filler particles and a binder, and the adhesive layer includes third polymer binder microsphere particles and a binder.

[0013] In some embodiments, based on the total mass of the porous coating as 100%, the mass fraction of the first filler particles is 70% to 84%, the mass fraction of the second microsphere filler particles is 1% to 15%, the mass fraction of the third polymer binder microsphere particles is 8% to 15%, and the mass fraction of the binder is 1% to 5%.

[0014] By making the mass ratio of the first filler particles and the second microsphere filler particles within the above range, it is beneficial to give full play to the high heat resistance of the first filler particles, and it is also beneficial to maintain the hollow structure of the second microsphere filler particles, so that the second microsphere filler particles can better play the role of storing and retaining the electrolyte. Therefore, by making the mass ratio of the first filler particles and the second microsphere filler particles within the above range, the separator can have high heat resistance, good electrolyte wettability and good electrolyte retention, which is beneficial to improve the problem of liquid swelling and interface purple spot lithium precipitation, and is beneficial for the electrochemical device to have both good thermal safety performance and good cycle performance. By making the mass fraction of the third polymer binder microsphere particles within the above range, the third polymer binder microsphere particles are beneficial to storing and retaining the electrolyte, and are also beneficial to improving the adhesion between the diaphragm and the electrode plate and the volume expansion of the buffer electrode plate, thereby helping to improve the thickness consistency of the electrochemical device, improve the electrolyte wettability at the corner interface, and improve the problem of purple spot lithium precipitation at the corner interface; in addition, by making the mass fraction of the third polymer binder microsphere particles within the above range, the diaphragm can also have a lower ionic impedance.

[0015] Optionally, based on the total mass of the porous coating as 100%, the mass fraction of the first filler particles is 70% to 80%, the mass fraction of the second microsphere filler particles is 5% to 15%, the mass fraction of the third polymer binder microsphere particles is 8% to 12%, and the mass fraction of the binder is 1% to 5%.

[0016] In some embodiments, the thickness variation rate of the porous coating during hot pressing at 85° C. and 1 MPa pressure for 20 seconds is 10% to 80%.

[0017] In some embodiments, the average thickness of the shell of the second microsphere filler particles is 50 nm to 200 nm, which can not only make the second microsphere filler particles easy to process and coat on the separator, but also provide more electrolyte storage space, improve the problem of electrolyte swelling and interface purple spot lithium precipitation, and improve the cycle performance of the electrochemical device.

[0018] In some embodiments, the diameter of the cavity of the second microsphere filler particle is 0.1 μm to 1.8 μm. This makes it easy to process the second microsphere filler particle and coat it on the separator, and provides more electrolyte storage space, improves the problem of electrolyte swelling and interface purple spot lithium precipitation, and improves the cycle performance of the electrochemical device.

[0019] In some embodiments, the specific surface area of ​​the second microsphere filler particles is 5 m 2 / g to 30m 2 / g.

[0020] In some embodiments, the average pore size of the pore structure of the shell of the second microsphere filler particle is less than 10 nm.

[0021] In some embodiments, the average thickness of the shell of the third polymer binder microsphere particles is 0.3 μm to 1 μm. This can not only buffer the volume expansion of the electrode plate, but also provide more electrolyte storage space, improve the problem of electrolyte swelling and interface purple spot lithium precipitation, especially the problem of corner interface purple spot lithium precipitation, and improve the cycle performance of the electrochemical device.

[0022] In some embodiments, the diameter of the cavity of the third polymer binder microsphere particles is 0.7 μm to 9.2 μm. This can not only buffer the volume expansion of the electrode plate, but also provide more electrolyte storage space, improve the problem of liquid swelling and interface purple spot lithium precipitation, especially the problem of corner interface purple spot lithium precipitation, and also make the diaphragm have better resistance to electrolyte swelling and lower ionic impedance, which is conducive to improving the cycle performance of the electrochemical device.

[0023] In some embodiments, the specific surface area of ​​the third polymer binder microsphere particles is 4 m 2 / g to 20m 2 / g.

[0024] In some embodiments, the pore structure of the outer shell of the third polymer binder microsphere particles has an average pore size of less than 10 nm.

[0025] In some embodiments, the glass transition temperature T g 60℃ to 100℃.

[0026] In some embodiments, the shell of the second microsphere filler particle includes a first shell layer and a second shell layer, the second shell layer is located between the first shell layer and the cavity of the second microsphere filler particle, the first shell layer includes polystyrene, the second shell layer includes an acrylic polymer, and the first shell layer and the second shell layer are connected by a CC covalent bond.

[0027] The first shell layer includes polystyrene, which can make the second microsphere filler particles have higher mechanical strength and better resistance to electrolyte swelling; the second shell layer includes acrylic polymer, which is easy to form a pore structure, thereby reducing the ionic impedance of the diaphragm, improving the liquid swelling problem and the interface purple spot lithium precipitation problem, and improving the cycle performance of the electrochemical device.

[0028] In some embodiments, the shell of the third polymer binder microsphere particle includes a third shell layer and a fourth shell layer, the fourth shell layer is located between the third shell layer and the cavity of the third polymer binder microsphere particle, the third shell layer includes polystyrene, the fourth shell layer includes an acrylic polymer, and the third shell layer and the fourth shell layer are connected by a CC covalent bond.

[0029] The third shell layer includes polystyrene, which can make the third polymer binder microsphere particles have higher mechanical strength and better resistance to electrolyte swelling; the fourth shell layer includes acrylic polymer, which is easy to form a pore structure, thereby reducing the ionic impedance of the diaphragm, improving the liquid swelling problem and the interface purple spot lithium precipitation problem, and improving the cycle performance of the electrochemical device.

[0030] In some embodiments, the first filler particles include at least one of boehmite, aluminum oxide, zirconium oxide, titanium dioxide, magnesium oxide, silicon oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, yttrium oxide, mullite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, barium sulfate, silicon carbide, silicon nitride, boron nitride, aluminum nitride, melamine, and dicyandiamide.

[0031] In some embodiments, the first filler particles are solid structures, which is helpful to improve the heat resistance of the separator and the thermal safety performance of the electrochemical device.

[0032] In some embodiments, the specific surface area of ​​the first filler particles is less than or equal to 20 m 2 / g. This is beneficial to improving the heat resistance of the diaphragm and the thermal safety performance of the electrochemical device.

[0033] In some embodiments, the glass transition temperature of the binder is g -40℃ to 15℃.

[0034] In some embodiments, the binder includes at least one of polymethacrylate binders, styrene-butadiene rubber, polyacrylic acid, and polyacrylate.

[0035] In some embodiments, the porous substrate has a thickness of 2 μm to 7 μm. A porous substrate having such a thickness is more conducive to improving the energy density of the electrochemical device.

[0036] In some embodiments, the thickness of the porous coating layer is 4 μm to 12 μm, which is more conducive to the electrochemical device having high energy density, good cycle performance and thermal safety performance.

[0037] In some embodiments, the total thickness of the separator is 6 μm to 19 μm.

[0038] In some embodiments, the bonding force between the porous substrate and the porous coating is 30 N / m to 100 N / m. The high bonding force between the porous substrate and the porous coating provides good stability of the separator, and the porous coating is not easy to fall off, which is more conducive to good cycle performance of the electrochemical device.

[0039] In a second aspect, the present application provides an electrochemical device, comprising a positive electrode sheet, a negative electrode sheet, and the diaphragm of the first aspect of the present application, wherein the diaphragm is located between the positive electrode sheet and the negative electrode sheet.

[0040] In some embodiments, the adhesion between the porous coating and the negative electrode plate is 5 N / m to 15 N / m when hot-pressed at 85° C. and 1 MPa for 60 seconds.

[0041] In some embodiments, the adhesion between the porous coating and the positive electrode sheet is 5 N / m to 20 N / m when hot-pressed at 85° C. and 1 MPa for 60 seconds.

[0042] In a third aspect, the present application provides an electronic device comprising the electrochemical device of the second aspect of the present application. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be clearly and completely described in conjunction with the embodiments below. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. The relevant embodiments described herein are illustrative in nature and are used to provide a basic understanding of the present application. The embodiments of the present application should not be interpreted as limiting the present application. Based on the technical scheme provided by the present application and the embodiments given, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present application.

[0044] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.

[0045] In the description herein, unless otherwise specified, “above” and “below” include the number.

[0046] Unless otherwise specified, the terms used in this application have the well-known meanings commonly understood by those skilled in the art. Unless otherwise specified, the values ​​of the parameters mentioned in this application can be measured by various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application). Unless otherwise specified, the test temperature of the parameters mentioned in this application is 25°C and the test pressure is standard atmospheric pressure.

[0047] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.

[0048] The term "plurality" means more than two.

[0049] The diaphragm is an important component of an electrochemical device. It separates the positive and negative electrodes and prevents contact short circuits in the electrochemical device. The diaphragm can also close its pores at a certain temperature, blocking the transmission of lithium ions and the flow of current, preventing direct contact and short circuits between the positive and negative electrodes, thereby reducing problems such as combustion and explosion in the electrochemical device. At the same time, the diaphragm also needs to be able to absorb and retain a certain amount of electrolyte in its pore structure, forming an ion transmission channel, realizing lithium ion migration, and completing the electrochemical charge and discharge process.

[0050] As the thickness of the diaphragm continues to decrease, the electrolyte storage space it can provide decreases, and the electrolyte's ability to retain electrolyte becomes worse. During the use of the electrochemical device, purple spots and lithium precipitation are prone to occur at the electrode plate interface, and even cause the electrochemical device to experience cycle diving. In particular, the interface gap at the corner of the electrochemical device is small. During the charge and discharge process, the corner is more likely to be squeezed and the electrolyte cannot penetrate, making it more likely to have purple spots and lithium precipitation at the corner interface.

[0051] At present, the diaphragm usually includes a porous substrate and a ceramic coating disposed on at least one side of the porous substrate. By increasing the porosity of the porous substrate, the electrolyte retention of the diaphragm can be improved. However, as the porosity of the porous substrate continues to increase, its structural strength deteriorates, the heat resistance of the diaphragm deteriorates, and the closed-cell characteristics of the diaphragm deteriorate, and it is unable to block the transmission of lithium ions and the flow of current when the electrochemical device is overheated, which may cause a direct contact short circuit between the positive and negative electrodes, which is not conducive to improving the thermal safety of the electrochemical device. Increasing the amount of electrolyte injection can easily lead to a liquid swelling problem after the electrochemical device is packaged, which will also affect the use of the electrochemical device.

[0052] Based on this, from the perspective of the diaphragm, the present application adjusts the composition of the porous coating of the diaphragm to enable the diaphragm to have high heat resistance, good electrolyte wettability and good electrolyte retention. When used in electrochemical devices, it can improve the problem of liquid swelling and the problem of purple lithium precipitation on the interface caused by electrolyte shortage, so that the electrochemical device can have both good cycle performance and thermal safety performance.

[0053] In a first aspect, an embodiment of the present application provides a diaphragm.

[0054] The separator provided in the embodiment of the present application includes a porous substrate and a porous coating disposed on at least one side of the porous substrate, wherein the porous coating includes first filler particles, second microsphere filler particles, third polymer binder microsphere particles and a binder. The first filler particles in the present application do not have a hollow structure.

[0055] The second microsphere filler particles include a cavity and a shell covering the cavity, the shell of the second microsphere filler particles includes multiple pore structures, and the average particle size of the second microsphere filler particles is 0.2μm to 2μm; the third polymer binder microsphere particles include a cavity and a shell covering the cavity, the shell of the third polymer binder microsphere particles includes multiple pore structures, and the average particle size of the third polymer binder microsphere particles is 1.5μm to 10μm.

[0056] The porous coating of the diaphragm of the present application includes second microsphere filler particles and third polymer binder microsphere particles. The second microsphere filler particles and the third polymer binder microsphere particles are hollow structures and the shell includes multiple pore structures. The pore structure connects the outside and the cavity, thereby increasing the porosity of the porous coating and making the porous coating and the diaphragm have lower ionic impedance; in addition, after liquid injection, the electrolyte can enter the cavity through the pore structure of the shell, thereby increasing the electrolyte storage space of the porous coating, allowing more electrolyte to be stored in the diaphragm, and improving the liquid swelling problem; in addition, during the cyclic charge and discharge process of the electrochemical device, especially in the late cycle, the electrolyte stored in the cavity can also be released through the pore structure of the shell, thereby reducing the problem of interfacial purple spot lithium precipitation caused by electrolyte shortage and improving the cycle performance of the electrochemical device using the diaphragm.

[0057] The average particle size of the second microsphere filler particles is too small (for example, less than 0.2 μm), which easily leads to a decrease in the accumulation pores of the second microsphere filler particles, affecting ion transmission, thereby affecting the cycle performance of the electrochemical device, and at the same time increasing the difficulty of preparing the second microsphere filler particles and increasing the production cost. By making the average particle size of the second microsphere filler particles 0.2 μm to 2 μm, the porous coating can have a higher packing density, thereby improving the heat resistance of the diaphragm and the thermal safety performance of the electrochemical device, and can also make the porous coating have more pores, thereby improving the ion transmission characteristics of the diaphragm and improving the cycle performance of the electrochemical device.

[0058] The third polymer binder microsphere particles have adhesive properties and can bond the diaphragm to the electrode plate.

[0059] The average particle size of the third polymer binder microsphere particles is small (for example, less than 1.5 μm), which is not conducive to the bonding between the diaphragm and the electrode plate; the average particle size of the third polymer binder microsphere particles is too large (for example, greater than 10 μm), and its extrusion resistance becomes poor, and it is easy to deform under the expansion force of the electrode plate, thereby reducing its ability to store and retain electrolyte. By making the average particle size of the third polymer binder microsphere particles 1.5 μm to 10 μm, the diaphragm and the electrode plate can be bonded, thereby improving the thickness consistency of the electrochemical device, and a certain gap (also known as Gap) can be formed between the diaphragm and the electrode plate, which can buffer the volume expansion of the electrode plate, improve the electrolyte wettability at the corner interface, improve the problem of purple spot lithium precipitation at the corner interface, improve the cycle performance of the electrochemical device, and also make the electrochemical device have a higher energy density.

[0060] The porous coating layer of the separator of the present application further includes first filler particles, which can improve the heat resistance of the separator.

[0061] Therefore, the diaphragm provided in the embodiment of the present application has high heat resistance, high adhesion, good electrolyte wettability and good electrolyte liquid retention. When used in electrochemical devices, it can improve the problem of liquid swelling and the problem of purple spot lithium precipitation on the interface, so that the electrochemical device can have both good cycle performance and thermal safety performance.

[0062] The average particle size of the second microsphere filler particles is 0.2μm to 2μm, for example, it can be 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2μm, or a range consisting of any of the above numerical values.

[0063] Optionally, the average particle size of the second microsphere filler particles can be 0.3μm to 2μm, 0.3μm to 1.8μm, 0.3μm to 1.6μm, 0.3μm to 1.4μm, 0.3μm to 1.2μm, 0.3μm to 1μm, 0.4μm to 2μm, 0.4μm to 1.8μm, 0.4μm to 1.6μm, 0.4μm to 1.4μm, 0.4μm to 1.2μm, 0.4μm to 1μm, 0.5μm to 2μm, 0.5μm to 1.8μm, 0.5μm to 1.6μm, 0.5μm to 1.4μm, 0.5μm to 1.2μm, 0.5μm to 1μm.

[0064] The second microsphere filler particles meeting this range are more conducive to improving the cycle performance and energy density of the electrochemical device.

[0065] The average particle size of the third polymer binder microsphere particles is 1.5μm to 10μm, for example, it can be 1.5μm, 1.8μm, 2μm, 2.4μm, 2.8μm, 3.2μm, 3.6μm, 4μm, 4.4μm, 4.8μm, 5.2μm, 5.6μm, 6μm, 6.4μm, 6.8μm, 7.2μm, 7.6μm, 8μm, 8.4μm, 8.8μm, 9.2μm, 9.6μm, 10μm, or a range consisting of any of the above numerical values.

[0066] Optionally, the average particle size of the third polymer binder microsphere particles can be 2μm to 10μm, 2.4μm to 10μm, 2.6μm to 10μm, 2.8μm to 10μm, 3μm to 10μm, 3.2μm to 10μm, 3.4μm to 10μm, 3.6μm to 10μm, 3.8μm to 10μm, 4μm to 10μm, 1.5μm to 8μm, 2μm to 8μm, 2.4μm to 8μm, 2.6μm to 8μm, 2.8μm to 8μm, 3μm to 8μm, 3.2μm to 8μm, 3.4μm to 8μm, 3.6μm to 8μm, 3.8μm to 8μm, 4μm to 8μm.

[0067] The third polymer binder microsphere particles meeting this range are more conducive to improving the cycle performance and energy density of the electrochemical device.

[0068] In some embodiments, the third polymeric binder microsphere particles have an average particle size greater than an average particle size of the second microsphere filler particles.

[0069] By making the average particle size of the third polymer binder microsphere particles larger than the average particle size of the second microsphere filler particles, the diaphragm and the electrode plates can be better bonded, and a sufficient gap can be formed between the diaphragm and the electrode plates to buffer the volume expansion of the electrode plates, thereby better improving the electrolyte wettability at the corner interface and improving the problem of purple spot lithium precipitation at the corner interface.

[0070] In some embodiments, the average particle size of the first filler particles can be 0.2μm to 2μm, for example, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2μm, or a range consisting of any of the above values.

[0071] If the average particle size of the first filler particles is too small (e.g., less than 0.2 μm), it is easy to reduce the pores of the first filler particles, affect ion transmission, and thus affect the cycle performance of the electrochemical device. By making the average particle size of the first filler particles 0.2 μm to 2 μm, the electrochemical device can have a higher energy density, and the porous coating can have a higher stacking density, thereby improving the heat resistance of the diaphragm and the thermal safety performance of the electrochemical device. The porous coating can also have more pores, thereby improving the ion transmission characteristics of the diaphragm and the cycle performance of the electrochemical device.

[0072] Optionally, the average particle size of the first filler particles may be 0.3 μm to 2 μm, 0.3 μm to 1.8 μm, 0.3 μm to 1.6 μm, 0.3 μm to 1.4 μm, 0.3 μm to 1.2 μm, 0.3 μm to 1 μm, 0.4 μm to 2 μm, 0.4 μm to 1.8 μm, 0.4 μm to 1.6 μm, 0.4 μm to 1.4 μm, 0.4 μm to 1.2 μm, 0. .4μm to 1μm, 0.5μm to 2μm, 0.5μm to 1.8μm, 0.5μm to 1.6μm, 0.5μm to 1.4μm, 0.5μm to 1.2μm, 0.5μm to 1μm, 0.6μm to 2μm, 0.6μm to 1.8μm, 0.6μm to 1.6μm, 0.6μm to 1.4μm, 0.6μm to 1.2μm, 0.6μm to 1μm.

[0073] The first filler particles meeting this range are more conducive to improving the thermal safety performance and cycle performance of the electrochemical device.

[0074] In some embodiments, the first filler particles are solid structures, which is helpful to improve the heat resistance of the separator and the thermal safety performance of the electrochemical device.

[0075] In the present application, the first filler particles being a solid structure does not mean that the first filler particles are absolutely non-porous, and the first filler particles may also be a nearly solid structure.

[0076] In some embodiments, the specific surface area of ​​the first filler particles may be less than or equal to 20 m 2 / g. This is beneficial to improving the heat resistance of the diaphragm and the thermal safety performance of the electrochemical device.

[0077] Optionally, the specific surface area of ​​the first filler particles may be less than or equal to 15 m 2 / g, less than or equal to 10m 2 / g.

[0078] In some embodiments, the specific surface area of ​​the second microsphere filler particles can be 5m 2 / g to 30m 2 / g, for example, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g, 17m 2 / g, 18m 2 / g, 19m 2 / g, 20m 2 / g, 21m 2 / g, 22m 2 / g, 23m 2 / g, 24m 2 / g, 25m 2 / g, 26m 2 / g, 27m 2 / g, 28m 2 / g, 29m 2 / g, 30m 2 / g, or any range consisting of the above values.

[0079] The second microsphere filler particles meeting the specific surface area range are beneficial to improving the liquid swelling problem and the purple spot lithium precipitation problem on the interface, and are beneficial to improving the cycle performance of the electrochemical device.

[0080] In some embodiments, the average pore size of the pore structure of the shell of the second microsphere filler particle may be less than 10 nm.

[0081] When the average pore size of the pore structure of the shell of the second microsphere filler particle meets the range of the present application, the liquid retention capacity and liquid storage effect of the second microsphere filler particle can be within a suitable range, thereby facilitating further improving the cycle performance of the electrochemical device.

[0082] In some embodiments, the specific surface area of ​​the third polymer binder microsphere particles can be 4 m 2 / g to 20m 2 / g, for example, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g, 17m 2 / g, 18m 2 / g, 19m 2 / g, 20m 2 / g, or any range consisting of the above values.

[0083] The third polymer binder microsphere particles meeting this specific surface area range are beneficial to improving the liquid swelling problem and the interface purple spot lithium precipitation problem, and are beneficial to improving the cycle performance of the electrochemical device.

[0084] In some embodiments, the average pore size of the pore structure of the shell of the third polymer binder microsphere particle may be less than 10 nm.

[0085] When the average pore size of the pore structure of the shell of the third polymer binder microsphere particles meets the range of the present application, the liquid retention capacity and liquid storage effect of the third polymer binder microsphere particles can be within a suitable range, which is beneficial to further improve the cycle performance of the electrochemical device.

[0086] In some embodiments, the third polymer binder microsphere particles are embedded in the pores formed by the accumulation of the first filler particles and the second microsphere filler particles and form protrusions on the surface of the porous coating.

[0087] In some embodiments, the porous coating includes a heat-resistant layer and an adhesive layer, the heat-resistant layer is arranged on at least one side of the porous substrate, the adhesive layer is arranged on at least a portion of the surface of the heat-resistant layer, the heat-resistant layer includes first filler particles, second microsphere filler particles and a binder, and the adhesive layer includes third polymer binder microsphere particles and a binder.

[0088] In some embodiments, based on the total mass of the porous coating as 100%, the mass fraction of the first filler particles can be 70% to 84%, for example, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, or a range consisting of any of the above values.

[0089] In some embodiments, based on the total mass of the porous coating as 100%, the mass fraction of the second microsphere filler particles can be 1% to 15%, for example, 1%, 2%, 3%, 4%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 11%, 12%, 13%, 14%, 15%, or a range consisting of any of the above values.

[0090] In some embodiments, based on the total mass of the porous coating as 100%, the mass fraction of the third polymer binder microsphere particles can be 8% to 15%, for example, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, or a range consisting of any of the above values.

[0091] By making the mass ratio of the first filler particles and the second microsphere filler particles within the above range, it is beneficial to give full play to the high heat resistance of the first filler particles, and it is also beneficial to maintain the hollow structure of the second microsphere filler particles, so that the second microsphere filler particles can better play the role of storing and retaining the electrolyte. Therefore, by making the mass ratio of the first filler particles and the second microsphere filler particles within the above range, the separator can have high heat resistance, good electrolyte wettability and good electrolyte retention, which is beneficial to improve the problem of liquid swelling and interface purple spot lithium precipitation, and is beneficial for the electrochemical device to have both good thermal safety performance and good cycle performance.

[0092] By making the mass fraction of the third polymer binder microsphere particles within the above range, the third polymer binder microsphere particles are beneficial to storing and retaining the electrolyte, and are also beneficial to improving the adhesion between the diaphragm and the electrode plate and the volume expansion of the buffer electrode plate, thereby helping to improve the thickness consistency of the electrochemical device, improve the electrolyte wettability at the corner interface, and improve the problem of purple spot lithium precipitation at the corner interface; in addition, by making the mass fraction of the third polymer binder microsphere particles within the above range, the diaphragm can also have a lower ionic impedance.

[0093] Optionally, based on 100% of the total mass of the porous coating layer, the mass fraction of the first filler particles may be 70% to 84%.

[0094] Optionally, based on 100% of the total mass of the porous coating layer, the mass fraction of the second microsphere filler particles may be 5% to 15%.

[0095] Optionally, based on 100% of the total mass of the porous coating layer, the mass fraction of the third polymer binder microsphere particles may be 8% to 12%.

[0096] In some embodiments, based on the total mass of the porous coating as 100%, the mass fraction of the binder can be 1% to 5%, for example, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or a range consisting of any of the above values.

[0097] The binder is used to bind the first filler particles, the second microsphere filler particles, and the third polymer binder microsphere particles to the porous substrate. By making the mass fraction of the binder within the above range, each particle in the porous coating layer can be firmly bonded to the porous substrate, reducing the problem of powder falling.

[0098] In some embodiments, the thickness change rate of the porous coating under hot pressing at 85°C and 1 MPa pressure for 20 seconds can be 10% to 80%, for example, it can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, or a range composed of any of the above values.

[0099] The thickness change rate of the porous coating at 85°C and 1Mpa pressure for 20s can be tested as follows: punch the diaphragm into a sample with a width of 50mm and a length of 100mm, then use two pieces of Teflon (PTFE) film of the same size to form a "sandwich" structure with the sample, and heat press for 20s (seconds) in a hot press at 85°C and 1Mpa pressure, finally separate the sample from the Teflon film, and test the thickness D2 of the porous coating of the diaphragm after hot pressing. The thickness change rate of the porous coating at 85°C and 1Mpa pressure for 20s = (D1-D2) / D1*100%, D1 is the thickness of the porous coating of the diaphragm before hot pressing.

[0100] The thickness of the porous coating refers to the distance between the surface of the second microsphere filler particles and the third polymer binder microsphere particles with a larger average particle size away from the porous substrate and the porous substrate. For example, the average particle size of the third polymer binder microsphere particles is greater than the average particle size of the second microsphere filler particles, and the thickness of the porous coating refers to the distance between the surface of the third polymer binder microsphere particles away from the porous substrate and the porous substrate. For accuracy, the distance between the surface of more than 10 particles away from the porous substrate and the porous substrate can be measured during the test, and then the average value is taken as the thickness of the porous coating.

[0101] [First filler particles]

[0102] In some embodiments, the first filler particles may include at least one of inorganic particles and organic particles, and may optionally include inorganic particles.

[0103] In some embodiments, the inorganic particles may include ceramic particles. As an example, the ceramic particles may include, but are not limited to, at least one of boehmite, aluminum oxide, zirconium oxide, titanium dioxide, magnesium oxide, silicon oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, yttrium oxide, mullite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, barium sulfate, silicon carbide, silicon nitride, boron nitride, and aluminum nitride.

[0104] In some embodiments, the organic particles may include at least one of melamine and dicyandiamide.

[0105] [Second microsphere filler particles]

[0106] In some embodiments, the average thickness of the shell of the second microsphere filler particle can be 50nm to 200nm, for example, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, or a range consisting of any of the above values.

[0107] The greater the thickness of the shell of the second microsphere filler particle, the smaller the electrolyte storage space that can be provided, and the smaller the improvement effect on the problem of liquid swelling and the problem of purple spot lithium precipitation at the interface; at the same time, the thickness of the shell of the second microsphere filler particle should not be too small. On the one hand, the difficulty of preparing the second microsphere filler particles increases and the production cost increases. On the other hand, the structural strength and processing performance of the second microsphere filler particles deteriorate, and the risk of shell deformation and rupture increases during the diaphragm preparation process, the electrochemical device assembly process, and the electrochemical device cyclic charge and discharge process. The present application makes the average thickness of the shell of the second microsphere filler particle 50nm to 200nm, which can not only make the second microsphere filler particles easy to process and easy to coat on the diaphragm, but also provide more electrolyte storage space, improve the problem of liquid swelling and the problem of purple spot lithium precipitation at the interface, and improve the cycle performance of the electrochemical device.

[0108] Optionally, the average thickness of the shell of the second microsphere filler particle can be 50nm to 150nm, 50nm to 120nm, 50nm to 100nm, 60nm to 150nm, 60nm to 120nm, 60nm to 100nm, 70nm to 150nm, 70nm to 120nm, 70nm to 100nm, 80nm to 150nm, 80nm to 120nm, 80nm to 100nm.

[0109] The second microsphere filler particles meeting this range are more conducive to improving the cycle performance of the electrochemical device.

[0110] In some embodiments, the diameter of the cavity of the second microsphere filler particle can be 0.1μm to 1.8μm, for example, 0.1μm, 0.15μm, 0.2μm, 0.25μm, 0.3μm, 0.35μm, 0.4μm, 0.45μm, 0.5μm, 0.55μm, 0.6μm, 0.65μm, 0.7μm, 0.75μm, 0.8μm, 0.85μm, 0.9μm, 0.95μm, 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, or a range composed of any of the above numerical values.

[0111] The diameter of the cavity of the second microsphere filler particle is small, and the electrolyte storage space that can be provided is small, and the improvement effect on the liquid swelling problem and the interface purple spot lithium precipitation problem is small; at the same time, the diameter of the cavity of the second microsphere filler particle should not be too large, at this time the structural strength and processing performance of the second microsphere filler particle deteriorate, and the risk of shell deformation and rupture increases during the diaphragm preparation process, the electrochemical device assembly process, and the electrochemical device cyclic charge and discharge process. The present application makes the diameter of the cavity of the second microsphere filler particle 0.1μm to 1.8μm, which can make the second microsphere filler particle easy to process and easy to coat on the diaphragm, and can provide more electrolyte storage space, improve the liquid swelling problem and the interface purple spot lithium precipitation problem, and improve the cycle performance of the electrochemical device.

[0112] Optionally, the diameter of the cavity of the second microsphere filler particle can be 0.2μm to 1.8μm, 0.3μm to 1.8μm, 0.4μm to 1.8μm, 0.1μm to 1.5μm, 0.2μm to 1.5μm, 0.3μm to 1.5μm, 0.4μm to 1.5μm, 0.1μm to 1μm, 0.2μm to 1μm, 0.3μm to 1μm, 0.4μm to 1μm, 0.1μm to 0.9μm, 0.2μm to 0.9μm, 0.3μm to 0.9μm, 0.4μm to 0.9μm, 0.1μm to 0.8μm, 0.2μm to 0.8μm, 0.3μm to 0.8μm, 0.4μm to 0.8μm.

[0113] The second microsphere filler particles meeting this range are more conducive to improving the cycle performance of the electrochemical device.

[0114] In some embodiments, the ratio of the diameter of the cavity of the second microsphere filler particles to the average particle size of the second microsphere filler particles can be 0.5:1 to 0.9:1, for example, 0.5:1, 0.52:1, 0.54:1, 0.56:1, 0.58:1, 0.6:1, 0.62:1, 0.64:1, 0.66:1, 0.68:1, 0.7:1, 0.72:1, 0.74:1, 0.76:1, 0.78:1, 0.8:1, 0.82:1, 0.84:1, 0.86:1, 0.88:1, 0.9:1, or a range consisting of any of the above values.

[0115] The ratio of the diameter of the cavity of the second microsphere filler particles to the average particle size of the second microsphere filler particles is small, and the electrolyte storage space that can be provided is small, and the improvement effect on the liquid swelling problem and the interface purple spot lithium precipitation problem is small; at the same time, the ratio of the diameter of the cavity of the second microsphere filler particles to the average particle size of the second microsphere filler particles should not be too large. On the one hand, the difficulty of preparing the second microsphere filler particles increases and the production cost increases. On the other hand, the structural strength and processing performance of the second microsphere filler particles deteriorate, and the risk of shell deformation and rupture increases during the diaphragm preparation process, the electrochemical device assembly process, and the electrochemical device cycle charge and discharge process. In this application, by making the ratio of the diameter of the cavity of the second microsphere filler particles to the average particle size of the second microsphere filler particles be 0.5:1 to 0.9:1, the second microsphere filler particles can be easily processed and easily coated on the diaphragm, and more electrolyte storage space can be provided, the liquid swelling problem and the interface purple spot lithium precipitation problem can be improved, and the cycle performance of the electrochemical device can be improved.

[0116] Optionally, the ratio of the diameter of the cavity of the second microsphere filler particles to the average particle size of the second microsphere filler particles can be 0.54:1 to 0.9:1, 0.6:1 to 0.9:1, 0.64:1 to 0.9:1, 0.7:1 to 0.9:1, 0.5:1 to 0.88:1, 0.54:1 to 0.88:1, 0.6:1 to 0.88:1, 0.64:1 to 0.88:1, 0.7:1 to 0.88:1.

[0117] The second microsphere filler particles meeting this range are more conducive to improving the cycle performance of the electrochemical device.

[0118] In some embodiments, the shell of the second microsphere filler particle may include a first shell layer and a second shell layer, the second shell layer is located between the first shell layer and the cavity of the second microsphere filler particle, the first shell layer may include polystyrene, the second shell layer may include an acrylic polymer, and the first shell layer and the second shell layer are connected by a CC covalent bond.

[0119] The first shell layer includes polystyrene, which can make the second microsphere filler particles have higher mechanical strength and better resistance to electrolyte swelling; the second shell layer includes acrylic polymer, which is easy to form a pore structure, thereby reducing the ionic impedance of the diaphragm, improving the liquid swelling problem and the interface purple spot lithium precipitation problem, and improving the cycle performance of the electrochemical device.

[0120] The second shell layer includes an acrylate polymer, which in some embodiments may include soft monomer structural units and hard monomer structural units.

[0121] Optionally, the soft monomer structural unit may include at least one of an n-butyl acrylate structural unit, an n-pentyl acrylate structural unit, an isopentyl acrylate structural unit, an isooctyl acrylate structural unit, a 2-ethylhexyl acrylate structural unit, a 2-nonyl acrylate structural unit, an isononyl acrylate structural unit, a decyl acrylate structural unit, an undecyl acrylate structural unit, a lauryl acrylate structural unit, a tridecyl acrylate structural unit, an octadecyl acrylate structural unit, a decyl methacrylate structural unit, an undecyl methacrylate structural unit, a lauryl methacrylate structural unit, a tridecyl methacrylate structural unit, and an octadecyl methacrylate structural unit.

[0122] Optionally, the hard monomer structural unit may include at least one of a methyl acrylate structural unit, a methyl methacrylate structural unit, a vinyl acetate structural unit, an acrylonitrile structural unit, an acrylamide structural unit, and a styrene structural unit.

[0123] Optionally, the mass ratio of the soft monomer structural unit to the hard monomer structural unit can be 40:60 to 20:80, for example, it can be 40:60, 39:61, 38:62, 37:63, 36:64, 35:65, 34:66, 33:67, 32:68, 31:69, 30:70, 29:71, 28:72, 27:73, 26:74, 25:75, 24:76, 23:77, 22:78, 21:79, 20:80, or a range consisting of any of the above numerical values.

[0124] Adjusting the mass ratio of the soft monomer structural unit to the hard monomer structural unit can make the second shell layer have better resistance to electrolyte swelling, which is beneficial for the porous coating and the separator to have lower ionic impedance.

[0125] In some embodiments, the acrylic polymer may further include a multi-functional cross-linking structural unit.

[0126] By making the acrylic polymer further include a multifunctional cross-linking structural unit, the mechanical strength and resistance to electrolyte swelling of the second shell layer can be improved, thereby improving the structural stability of the second microsphere filler particles and also facilitating the porous coating and the separator to have lower ionic resistance.

[0127] Optionally, the multifunctional cross-linking structural unit may include at least one of an ethylene glycol dimethacrylate structural unit, a polyethylene glycol dimethacrylate structural unit, a butylene glycol dimethacrylate structural unit, a hexanediol dimethacrylate structural unit, a polybutadiene dimethacrylate structural unit, a polyurethane dimethacrylate structural unit, a propoxylated glycerol trimethacrylate structural unit, and a divinylbenzene structural unit.

[0128] Optionally, the mass of the multi-functional cross-linked structural unit can be 0.1% to 10% of the total mass of the soft monomer structural unit and the hard monomer structural unit, for example, it can be 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or a range consisting of any of the above values.

[0129] In some embodiments, the acrylic polymer may further include functional monomer structural units.

[0130] Optionally, the functional monomer structural unit may include at least one of an acrylic acid structural unit, a methacrylic acid structural unit, an itaconic acid structural unit, a hydroxyethyl acrylate structural unit, a hydroxypropyl acrylate structural unit, a hydroxybutyl acrylate structural unit, and a glycidyl acrylate structural unit.

[0131] By making the acrylic ester polymer further include a functional monomer structural unit, the functional monomer structural unit contains a lyophilic group, thereby improving the electrolyte wettability of the second shell layer and reducing the ionic resistance of the separator.

[0132] Optionally, the mass of the functional monomer structural unit can be 1% to 20% of the total mass of the soft monomer structural unit and the hard monomer structural unit, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, or a range consisting of any of the above values.

[0133] In some embodiments, the method for preparing the second microsphere filler particles may include the following steps:

[0134] Through the seed polymerization method, a "nano seed" is polymerized to be used as a core, and the core includes an acrylic polymer;

[0135] Through interfacial polymerization, a coating layer is polymerized on the surface of the "nanoseed" to obtain latex particles with a core-shell structure, wherein the coating layer includes polystyrene;

[0136] The prepared core-shell structured emulsion particles are transferred to an acidic solution, an alkaline solution or an organic solvent, and the solvent penetrates through the coating layer to dissolve the core polymer material. During the dissolution process, the coating layer continues to expand, and the solvent penetrates the coating layer to form a through pore structure. The dissolved polymer material can be discharged through the pore structure to form a cavity of the second microsphere filler particle, and the remaining part (including the undissolved polymer material and the coating layer) serves as the shell of the second microsphere filler particle. The shell includes multiple pore structures, the shell includes a first shell layer and a second shell layer, the second shell layer is located between the first shell layer and the cavity, the first shell layer includes polystyrene, the second shell layer includes an acrylic polymer, and the first shell layer and the second shell layer are connected by a CC covalent bond.

[0137] [Third polymer binder microsphere particles]

[0138] The "third polymer binder microsphere particles" in the porous coating of the separator play a role in improving the adhesion between the separator and the electrode plate, and they are basically not resistant to high temperatures. In some embodiments, the glass transition temperature T g It may be from 60°C to 100°C.

[0139] In some embodiments, the average thickness of the shell of the third polymer binder microsphere particles can be 0.3μm to 1μm, for example, 0.3μm, 0.35μm, 0.4μm, 0.45μm, 0.5μm, 0.55μm, 0.6μm, 0.65μm, 0.7μm, 0.75μm, 0.8μm, 0.85μm, 0.9μm, 0.95μm, 1μm, or a range consisting of any of the above numerical values.

[0140] The thicker the shell of the third polymer binder microsphere particles is, the smaller the electrolyte storage space that can be provided, and the smaller the improvement effect on the liquid swelling problem and the interface purple spot lithium precipitation problem; at the same time, the thickness of the shell of the third polymer binder microsphere particles should not be too small, so as to provide good rebound ability when the volume of the electrode plate changes, and buffer the volume expansion of the electrode plate. By making the average thickness of the shell of the third polymer binder microsphere particles 0.3μm to 1μm, it can not only buffer the volume expansion of the electrode plate, but also provide more electrolyte storage space, improve the liquid swelling problem and the interface purple spot lithium precipitation problem, especially the corner interface purple spot lithium precipitation problem, and improve the cycle performance of the electrochemical device.

[0141] Optionally, the average thickness of the shell of the third polymer binder microsphere particles can be 0.3μm to 0.9μm, 0.3μm to 0.8μm, 0.3μm to 0.7μm, 0.3μm to 0.6μm, 0.35μm to 0.9μm, 0.35μm to 0.8μm, 0.35μm to 0.7μm, 0.35μm to 0.6μm.

[0142] The third polymer binder microsphere particles that meet this range are more conducive to improving the liquid swelling problem and the interface purple spot lithium precipitation problem, especially the corner interface purple spot lithium precipitation problem, and are more conducive to improving the cycle performance of the electrochemical device.

[0143] In some embodiments, the diameter of the cavity of the third polymer binder microsphere particles can be 0.7μm to 9.2μm, for example, it can be 0.7μm, 0.8μm, 0.9μm, 1μm, 1.2μm, 1.5μm, 1.8μm, 2μm, 2.2μm, 2.5μm, 2.8μm, 3μm, 3.2μm, 3.5μm, 3.8μm, 4μm, 4.2μm, 4.5μm, 4.8μm, 5μm, 5.2μm, 5.5μm, 5.8μm, 6μm, 6.2μm, 6.5μm, 6.8μm, 7μm, 7.2μm, 7.5μm, 7.8μm, 8μm, 8.2μm, 8.5μm, 8.8μm, 9μm, 9.2μm, or a range composed of any of the above numerical values.

[0144] The diameter of the cavity of the third polymer binder microsphere particles is small, the electrolyte storage space provided is small, the gap formed between the diaphragm and the electrode plate is small, and the improvement effect on the liquid swelling problem and the interface purple spot lithium precipitation problem, especially the corner interface purple spot lithium precipitation problem, is small; at the same time, the diameter of the cavity of the third polymer binder microsphere particles should not be too large, at this time, the electrolyte swelling resistance of the third polymer binder microsphere particles deteriorates, affecting the ionic impedance of the diaphragm. By making the diameter of the cavity of the third polymer binder microsphere particles 0.7μm to 9.2μm, it can buffer the volume expansion of the electrode plate, provide more electrolyte storage space, improve the liquid swelling problem and the interface purple spot lithium precipitation problem, especially the corner interface purple spot lithium precipitation problem, and also make the diaphragm have better electrolyte swelling resistance and lower ionic impedance, which is beneficial to improve the cycle performance of the electrochemical device.

[0145] Optionally, the diameter of the cavity of the third polymer binder microsphere particles can be 0.7μm to 9.2μm, 0.7μm to 8μm, 0.7μm to 7.2μm, 0.7μm to 6μm, 1.5μm to 9.2μm, 1.5μm to 8μm, 1.5μm to 7.2μm, 1.5μm to 6μm, 2μm to 9.2μm, 2μm to 8μm, 2μm to 7.2μm, 2μm to 6μm, 2.2μm to 9.2μm, 2.2μm to 8μm, 2.2μm to 7.2μm, 2.2μm to 6μm, 2.5μm to 9.2μm, 2.5μm to 8μm, 2.5μm to 7.2μm, 2.5μm to 6μm.

[0146] The third polymer binder microsphere particles meeting this range are more conducive to improving the cycle performance of the electrochemical device.

[0147] In some embodiments, the ratio of the diameter of the cavity of the third polymer binder microsphere particles to the average particle size of the third polymer binder microsphere particles can be 0.5:1 to 0.92:1, for example, 0.5:1, 0.52:1, 0.54:1, 0.56:1, 0.58:1, 0.6:1, 0.62:1, 0.64:1, 0.66:1, 0.68:1, 0.7:1, 0.72:1, 0.74:1, 0.76:1, 0.78:1, 0.8:1, 0.82:1, 0.84:1, 0.86:1, 0.88:1, 0.9:1, 0.92:1, or a range consisting of any of the above values.

[0148] The ratio of the diameter of the cavity of the third polymer binder microsphere particles to the average particle size of the third polymer binder microsphere particles is small, the electrolyte storage space that can be provided is small, and the gap formed between the diaphragm and the electrode plate is small, which has little effect on improving the liquid swelling problem and the interface purple spot lithium precipitation problem, especially the corner interface purple spot lithium precipitation problem; at the same time, the ratio of the diameter of the cavity of the third polymer binder microsphere particles to the average particle size of the third polymer binder microsphere particles should not be too large. On the one hand, the preparation difficulty and production cost of the third polymer binder microsphere particles are increased, and on the other hand, the third polymer binder microsphere particles have poor resistance to electrolyte swelling, which affects the ionic impedance of the diaphragm. The present application makes the ratio of the diameter of the cavity of the third polymer binder microsphere particles to the average particle size of the third polymer binder microsphere particles be 0.5:1 to 0.92:1, so that the third polymer binder microsphere particles can be easily processed and coated on the diaphragm, and more electrolyte storage space can be provided, thereby improving the problem of liquid swelling and the problem of purple spot lithium precipitation at the interface, especially the problem of purple spot lithium precipitation at the corner interface, and the diaphragm can also have better resistance to electrolyte swelling and lower ionic impedance, which is beneficial to improving the cycle performance of the electrochemical device.

[0149] Optionally, the ratio of the diameter of the cavity of the third polymer binder microsphere particles to the average particle size of the third polymer binder microsphere particles can be 0.54:1 to 0.92:1, 0.6:1 to 0.92:1, 0.64:1 to 0.92:1, 0.7:1 to 0.92:1, 0.5:1 to 0.9:1, 0.54:1 to 0.9:1, 0.6:1 to 0.9:1, 0.64:1 to 0.9:1, 0.7:1 to 0.9:1.

[0150] The third polymer binder microsphere particles meeting this range are more conducive to improving the cycle performance of the electrochemical device.

[0151] In some embodiments, the shell of the third polymer binder microsphere particle includes a third shell layer and a fourth shell layer, the fourth shell layer is located between the third shell layer and the cavity of the third polymer binder microsphere particle, the third shell layer includes polystyrene, the fourth shell layer includes an acrylic polymer, and the third shell layer and the fourth shell layer are connected by a CC covalent bond.

[0152] The third shell layer includes polystyrene, which can make the third polymer binder microsphere particles have higher mechanical strength and better resistance to electrolyte swelling; the fourth shell layer includes acrylic polymer, which is easy to form a pore structure, thereby reducing the ionic impedance of the diaphragm, improving the liquid swelling problem and the interface purple spot lithium precipitation problem, and improving the cycle performance of the electrochemical device.

[0153] The fourth shell layer includes an acrylic polymer. In some embodiments, the acrylic polymer may include soft monomer structural units and hard monomer structural units.

[0154] Optionally, the soft monomer structural unit may include at least one of an n-butyl acrylate structural unit, an n-pentyl acrylate structural unit, an isopentyl acrylate structural unit, an isooctyl acrylate structural unit, a 2-ethylhexyl acrylate structural unit, a 2-nonyl acrylate structural unit, an isononyl acrylate structural unit, a decyl acrylate structural unit, an undecyl acrylate structural unit, a lauryl acrylate structural unit, a tridecyl acrylate structural unit, an octadecyl acrylate structural unit, a decyl methacrylate structural unit, an undecyl methacrylate structural unit, a lauryl methacrylate structural unit, a tridecyl methacrylate structural unit, and an octadecyl methacrylate structural unit.

[0155] Optionally, the hard monomer structural unit may include at least one of a methyl acrylate structural unit, a methyl methacrylate structural unit, a vinyl acetate structural unit, an acrylonitrile structural unit, an acrylamide structural unit, and a styrene structural unit.

[0156] Optionally, the mass ratio of the soft monomer structural unit to the hard monomer structural unit can be 40:60 to 20:80, for example, it can be 40:60, 39:61, 38:62, 37:63, 36:64, 35:65, 34:66, 33:67, 32:68, 31:69, 30:70, 29:71, 28:72, 27:73, 26:74, 25:75, 24:76, 23:77, 22:78, 21:79, 20:80, or a range consisting of any of the above numerical values.

[0157] Adjusting the mass ratio of the soft monomer structural unit to the hard monomer structural unit can make the fourth shell layer have both good adhesion and good resistance to electrolyte swelling, which is beneficial for the porous coating and the separator to have lower ionic impedance.

[0158] In some embodiments, the acrylic polymer may further include a multi-functional cross-linking structural unit.

[0159] By making the acrylic polymer further include a multifunctional cross-linked structural unit, the mechanical strength and electrolyte swelling resistance of the fourth shell can be improved, thereby improving the structural stability of the third polymer binder microsphere particles, and also facilitating the porous coating and the separator to have lower ionic impedance.

[0160] Optionally, the multifunctional cross-linking structural unit may include at least one of an ethylene glycol dimethacrylate structural unit, a polyethylene glycol dimethacrylate structural unit, a butylene glycol dimethacrylate structural unit, a hexanediol dimethacrylate structural unit, a polybutadiene dimethacrylate structural unit, a polyurethane dimethacrylate structural unit, a propoxylated glycerol trimethacrylate structural unit, and a divinylbenzene structural unit.

[0161] Optionally, the mass of the multi-functional cross-linked structural unit can be 0.1% to 10% of the total mass of the soft monomer structural unit and the hard monomer structural unit, for example, it can be 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or a range consisting of any of the above values.

[0162] In some embodiments, the acrylic polymer may further include functional monomer structural units.

[0163] Optionally, the functional monomer structural unit may include at least one of an acrylic acid structural unit, a methacrylic acid structural unit, an itaconic acid structural unit, a hydroxyethyl acrylate structural unit, a hydroxypropyl acrylate structural unit, a hydroxybutyl acrylate structural unit, and a glycidyl acrylate structural unit.

[0164] By making the acrylic ester polymer further include a functional monomer structural unit, the functional monomer structural unit contains a lyophilic group, thereby improving the electrolyte wettability of the fourth shell layer and reducing the ionic resistance of the separator.

[0165] Optionally, the mass of the functional monomer structural unit can be 1% to 10% of the total mass of the soft monomer structural unit and the hard monomer structural unit, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or a range consisting of any of the above values.

[0166] In some embodiments, the method for preparing the third polymer binder microsphere particles may include the following steps:

[0167] Through the seed polymerization method, a "nano seed" is polymerized to be used as a core, and the core includes an acrylic polymer;

[0168] Through interfacial polymerization, a coating layer is polymerized on the surface of the "nanoseed" to obtain latex particles with a core-shell structure, wherein the coating layer includes polystyrene;

[0169] The prepared core-shell structured emulsion particles are transferred to an acidic solution, an alkaline solution or an organic solvent, and the solvent penetrates through the coating layer to dissolve the core polymer material. During the dissolution process, the coating layer continues to expand, and the solvent penetrates the coating layer to form a through pore structure. The dissolved polymer material can be discharged through the pore structure to form a cavity of the third polymer binder microsphere particle, and the remaining part (including the undissolved polymer material and the coating layer) serves as the shell of the third polymer binder microsphere particle, the shell includes a plurality of pore structures, the shell includes a third shell layer and a fourth shell layer, the fourth shell layer is located between the third shell layer and the cavity, the third shell layer includes polystyrene, the fourth shell layer includes an acrylic polymer, and the third shell layer and the fourth shell layer are connected by a CC covalent bond.

[0170] [Binder]

[0171] In some embodiments, the glass transition temperature of the binder is g The temperature may be between -40°C and 15°C, for example, -40°C, -35°C, -30°C, -25°C, -20°C, -15°C, -10°C, -5°C, 0°C, 5°C, 10°C, 15°C, or a range consisting of any of the above values.

[0172] In some embodiments, the binder may include, but is not limited to, at least one of polymethacrylate binders, styrene-butadiene rubber, polyacrylic acid, and polyacrylate.

[0173] In some embodiments, the porous coating may further include a wetting agent and / or a dispersant. The wetting agent and / or the dispersant may improve the consistency of the porous coating, thereby facilitating the reduction of the problem of purple lithium deposition at the interface.

[0174] The present application has no particular restrictions on the type and content of the dispersant and wetting agent, as long as the purpose of the present application can be achieved. Optionally, the dispersant may include but is not limited to at least one of sodium carboxymethyl cellulose, polyethylene glycol, polyvinyl pyrrolidone, polyvinyl alcohol compounds, and sodium dodecylbenzene sulfonate. Optionally, the wetting agent may include but is not limited to at least one of dimethyl siloxane, polyoxyethylene alkylphenol ether, polyoxyethylene fatty alcohol ether, polyoxyethylene polyoxypropylene block copolymer, and polyether-modified trimethyl siloxane.

[0175] In some embodiments, the thickness of the porous substrate may be 2 μm to 7 μm, for example, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, or any range thereof. A porous substrate having such a thickness is more conducive to improving the energy density of the electrochemical device.

[0176] In some embodiments, the porosity of the porous substrate may be 20% to 50%, for example, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50%, or any range thereof. A porosity satisfying this range is more conducive to improving the cycle performance of the electrochemical device.

[0177] The porosity of the porous substrate can be tested by a true density tester. Place the porous substrate sample on the true density tester for testing to obtain the true volume of the porous substrate. Use a ruler to measure the length, width, and height of the sample, and calculate the apparent volume of the porous substrate. Porosity of porous substrate (%) = (apparent volume of porous substrate - true volume of porous substrate) / apparent volume of porous substrate × 100%.

[0178] The present application has no particular restrictions on the material of the porous substrate, as long as the purpose of the present application can be achieved. For example, the porous substrate can be a non-woven fabric, a film or a composite film with a porous structure, and the material of the porous substrate can include at least one of polyethylene, polypropylene, polyethylene terephthalate, polyimide, polyamide, spandex and aramid. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film can be used.

[0179] The porous coating layer is disposed on at least one side of the porous substrate. For example, the porous coating layer may be disposed on one side of the porous substrate, or the porous coating layer may be disposed on both sides of the porous substrate.

[0180] In some embodiments, the thickness of the porous coating layer may be 4 μm to 12 μm, for example, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, or any range thereof. The thickness of the porous coating layer refers to the thickness of the porous coating layer located on one side of the porous substrate.

[0181] By making the thickness of the porous coating layer 4 μm to 12 μm, it is more advantageous for the electrochemical device to have high energy density, good cycle performance and thermal safety performance.

[0182] In some embodiments, the total thickness of the diaphragm can be 6μm to 19μm, for example, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, or a range consisting of any of the above values.

[0183] In some embodiments, the bonding force between the porous substrate and the porous coating can be 30 N / m to 100 N / m, for example, 30 N / m, 40 N / m, 50 N / m, 60 N / m, 70 N / m, 80 N / m, 90 N / m, 100 N / m, or a range consisting of any of the above values.

[0184] The bonding force between the porous substrate and the porous coating can be tested by a 180° peeling test according to GB / T 2790-1995, with a peeling speed of 50 mm / min.

[0185] The bonding force between the porous substrate and the porous coating is high, the stability of the separator is good, and the porous coating is not easy to fall off, which is more conducive to the electrochemical device having good cycle performance.

[0186] In some embodiments, the preparation method of the separator may include the following steps: providing a porous substrate; providing a slurry including first filler particles, second microsphere filler particles, third polymer binder microsphere particles and a binder; coating the slurry on at least one side of the porous substrate, and obtaining the separator after drying. After the slurry is dried, the third polymer binder microsphere particles are embedded in the pores formed by the accumulation of the first filler particles and the second microsphere filler particles and form protrusions on the surface of the porous coating.

[0187] Optionally, the solvent in the slurry may include water.

[0188] In some embodiments, the preparation method of the diaphragm may include the following steps: providing a porous substrate; providing a heat-resistant layer slurry including first filler particles, second microsphere filler particles and a binder, and a bonding layer slurry including third polymer binder microsphere particles and a binder; coating the heat-resistant layer slurry on at least one side of the porous substrate, coating the bonding layer slurry on the surface of the heat-resistant layer after drying, and then drying to obtain the diaphragm.

[0189] Optionally, the solvent in the heat-resistant layer slurry and the bonding layer slurry may include water.

[0190] The average particle size of each of the above particles (such as the first filler particles, the second microsphere filler particles, the third polymer binder microsphere particles, etc.) can be tested as follows: use a scanning electron microscope to refer to JY / T010-1996, obtain the SEM image of the diaphragm, arbitrarily select a test sample with a length × width of 50mm × 100mm on the diaphragm, randomly select multiple test areas (for example, 5) in the test sample, and read the particle size of each particle in each test area at a certain magnification (for example, more than 500 times); count the number of particles and particle size values ​​in each test area, and take the arithmetic mean of the particle size of all particles in each test area as the average particle size of the particles. In order to ensure the accuracy of the test results, multiple test samples (for example, 10) can be taken for the above test, and the average value of each test sample is taken as the final test result. The testing instrument can be ZEISS Sigma 300. It should be noted that when the particle is irregular in shape, the distance between the two farthest points on the particle is taken as the particle size of the particle.

[0191] The diameter of the cavity of the microsphere particles (such as the second microsphere filler particles and the third polymer binder microsphere particles) refers to the straight-line distance passing through the center of the hollow cavity and extending to both ends of the hollow cavity. It can be measured by taking the average value after taking multiple (for example, more than 50) positions in the diaphragm cross-section image.

[0192] The thickness of the shell of the microsphere particles (such as the second microsphere filler particles and the third polymer binder microsphere particles) refers to the distance between the inner surface and the outer surface of the microsphere particles. The distance between the inner surface and the outer surface of the microsphere particles can be measured at multiple positions (for example, more than 50) in the diaphragm cross-section image and then the average value is taken.

[0193] The specific surface area of ​​the above particles (such as the first filler particles, the second microsphere filler particles, the third polymer binder microsphere particles, etc.) can be measured by nitrogen adsorption method using a specific surface area analyzer (such as TristarⅡ3020M) with reference to GB / T 19587-2017.

[0194] Glass transition temperature T g The test was conducted by differential scanning calorimetry (DSC). Test conditions: nitrogen atmosphere, heating rate 10°C / min.

[0195] Electrochemical Devices

[0196] In a second aspect, the present invention provides an electrochemical device, including any device in which an electrochemical reaction occurs to convert chemical energy into electrical energy, and its specific examples include all kinds of lithium primary batteries or lithium secondary batteries. In particular, lithium secondary batteries include lithium ion secondary batteries.

[0197] During the use of electrochemical devices, oxidation and reduction reactions of electrode active materials occur with charging and discharging. The negative electrode is an electrode that absorbs or lithiates lithium ions during charging and releases or delithiates lithium during discharging. The positive electrode is an electrode that releases or delithiates lithium ions during charging and absorbs or lithiates lithium during discharging.

[0198] In some embodiments, the electrochemical device may include a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator, the separator is located between the positive electrode sheet and the negative electrode sheet, and the separator used in the electrochemical device is the separator of the first aspect of the embodiment of the present application. Therefore, the electrochemical device provided in the embodiment of the present application can have good cycle performance.

[0199] The positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly through a winding process or a lamination process.

[0200] In some embodiments, the bonding strength between the porous coating of the separator and the negative electrode plate in a hot pressing test at 85° C. and 1 MPa pressure for 60 seconds may be 5 N / m to 15 N / m.

[0201] In some embodiments, the bonding strength between the porous coating of the separator and the positive electrode plate in a hot pressing test at 85° C. and 1 MPa pressure for 60 seconds may be 5 N / m to 20 N / m.

[0202] The bonding strength between the porous coating of the diaphragm and the electrode plate (for example, the negative electrode plate or the positive electrode plate) tested by hot pressing for 60 seconds at 85°C and 1 MPa pressure can be tested as follows: the diaphragm and the electrode plate are punched into samples with a width of 15 mm and a length of 20 cm to 30 cm, and then the porous coating of the diaphragm is aligned and bonded to the surface of the electrode plate, and then hot pressed for 60 seconds (seconds) in a hot press at 85°C and 1 MPa pressure. Finally, the hot-pressed diaphragm and electrode plate complex is taken out, and a 180° peeling test is performed on a tensile testing machine to obtain the bonding strength, and the peeling speed is 50 mm / min.

[0203] The electrochemical device also includes an outer package for packaging the electrode assembly and the electrolyte. In some embodiments, the outer package can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc., or a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as at least one of aluminum-plastic film, polypropylene, polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0204] The electrolyte may include an electrolyte salt and a solvent, wherein the electrolyte salt contains lithium ions. The types of the electrolyte salt and the solvent are not particularly limited and may be selected according to requirements.

[0205] In some embodiments, the electrolyte salt may include, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), and lithium dioxalatoborate (LiBOB). The above electrolyte salts may be used alone or in combination of two or more.

[0206] In some embodiments, the solvent may include at least one of a carbonate compound, a carboxylate compound, an ether compound, and a sulfone compound. As an example, the solvent may include, but is not limited to, ethylene carbonate (EC), fluoroethylene carbonate (FEC), vinylene carbonate (VC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate ( MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), γ-butyrolactone, sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), diethyl sulfone (ESE), methyl sulfolane, dimethyl sulfoxide, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl ether, diethyl ether, nitromethane, N,N-dimethylformamide. The above solvents can be used alone or in combination of two or more.

[0207] The electrolyte can be prepared by conventional methods in the art. For example, the components such as the solvent and the electrolyte salt can be mixed uniformly to obtain the electrolyte. There is no particular restriction on the order of adding the materials. For example, the components such as the electrolyte salt can be added to the solvent and mixed uniformly to obtain the electrolyte.

[0208] The components and their contents in the electrolyte can be determined by conventional methods in the art, for example, by gas chromatography-mass spectrometry (GC-MS), ion chromatography (IC), liquid chromatography (LC), etc.

[0209] [Positive electrode]

[0210] The material, composition and manufacturing method of the positive electrode sheet may include any technology known in the prior art.

[0211] In some embodiments, the positive electrode sheet may include a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector.

[0212] In some embodiments, the positive electrode current collector may be in the shape of a plate or foil, which is not limited in the embodiments of the present application.

[0213] In some embodiments, the thickness of the positive electrode current collector may be 6 μm to 25 μm.

[0214] In some embodiments, the material of the positive electrode current collector is not particularly limited, and a material with electronic conductivity can be selected. For example, a single substance or alloy (such as stainless steel, etc.) containing at least one element of C, Ti, Cr, Mo, Ru, Rh, Ta, W, Os, Ir, Pt, Au, and Al can be used.

[0215] From the viewpoint of high conductivity, high stability in electrolyte and good oxidation resistance, C layer, Al foil, stainless steel foil, etc. are optional. From the viewpoint of further reducing production cost, Al foil is optional. Those skilled in the art can adjust according to actual conditions.

[0216] The positive electrode active material layer includes a positive electrode active material, and the positive electrode active material may be selected from materials capable of absorbing and releasing lithium.

[0217] The specific type of the positive electrode active material is not particularly limited and can be selected according to needs. As an example, the positive electrode active material may include, but is not limited to, lithium iron phosphate (LiFePO4), lithium manganese phosphate (LiMnPO4), lithium cobalt phosphate (LiCoPO4), iron pyrophosphate (Li2FeP2O7), lithium cobalt oxide (LiCoO2), spinel lithium manganese oxide (LiMn2O4), spinel lithium nickel manganese oxide, layered lithium manganese oxide (LiMnO2), lithium nickel oxide (LiNiO2), lithium niobate (LiNbO2), lithium ferrite (LiFeO2), lithium magnesium oxide (LiMgO2), lithium calcium oxide (LiCaO2), lithium copper oxide (LiCuO2), lithium zinc oxide (LiZnO2), lithium molybdate (LiMoO2), lithium tantalate (LiTaO2), lithium tungstate (LiWO2), lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium-rich materials (e.g., lithium-rich nickel cobalt manganese oxide), manganese oxide (MnO2), vanadium oxide, sulfur oxide, silicate oxide, and at least one of their respective modified compounds. These materials may be used alone or in combination of two or more.

[0218] Optionally, the positive electrode active material may include at least one of lithium iron phosphate (LiFePO4), lithium cobalt oxide (LiCoO2), lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, spinel-type lithium nickel manganese oxide, and their respective modified compounds.

[0219] As an example, the molecular formula of lithium nickel cobalt aluminum oxide may be LiNi x Co y Al 1-x-y O2, where 0 < x < 1, 0 < y < 1, 0 < x + y < 1. For example, it may include but is not limited to LiNi 0.8 Co 0.15 Al 0.05 O2.

[0220] As an example, the molecular formula of lithium nickel cobalt manganese oxide may be LiNi x Co y Mn 1-x-y O2, where 0 < x < 1, 0 < y < 1, 0 < x + y < 1. For example, it may include but is not limited to LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, or at least one of them.

[0221] As an example, spinel-type lithium nickel manganese oxide may include but is not limited to LiNi 0.5 Mn 1.5 O4.

[0222] The modified compounds of the above positive electrode active materials may be doping modification, surface coating modification, or simultaneous doping and coating modification of the positive electrode active material.

[0223] In some embodiments, the porosity of the positive electrode active material layer may be 20% to 35%.

[0224] In some embodiments, the thickness of the positive electrode active material layer may be 15 μm to 150 μm, which is not limited in the embodiments of the present application. The thickness of the positive electrode active material layer refers to the thickness of the positive electrode active material layer on one side of the positive electrode current collector.

[0225] In some embodiments, the positive electrode active material layer may include a positive electrode conductive agent. The positive electrode conductive agent may include conductive carbon powder. As an example, the positive electrode conductive agent may include, but is not limited to, at least one of conductive carbon black, acetylene black (AB), Ketjen black (KB), graphite, carbon fiber, carbon tube, graphene, amorphous carbon, hard carbon, soft carbon, glassy carbon, carbon nanofiber, and carbon nanotube (CNT). These materials may be used alone or in combination of two or more.

[0226] In some embodiments, the positive electrode active material layer may include a positive electrode binder. The positive electrode binder may include, but is not limited to, at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and polyvinyl alcohol (PVA).

[0227] The positive electrode sheet can be prepared according to conventional methods in the art. Usually, the positive electrode active material, positive electrode conductive agent, positive electrode binder, etc. are dispersed in a solvent to form a positive electrode slurry, and the positive electrode slurry is coated on the positive electrode collector, and the positive electrode sheet is obtained through processes such as drying and compaction. The solvent can be N-methylpyrrolidone (NMP), but the present application is not limited thereto.

[0228] The coating method may be a coating method known in the art, such as extrusion coating, gravure coating, micro-gravure coating, electrospraying, transfer coating, etc., which is not limited in the embodiments of the present application.

[0229] [Negative electrode]

[0230] The material, composition and manufacturing method of the negative electrode sheet may include any technology known in the prior art.

[0231] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector.

[0232] In some embodiments, the shape of the negative electrode current collector may be plate-shaped or foil-shaped, which is not limited in the embodiments of the present application.

[0233] In some embodiments, the thickness of the negative electrode current collector may be 4 μm to 25 μm.

[0234] In some embodiments, the material of the negative electrode current collector is not particularly limited, and a material with good electronic conductivity can be selected. For example, a single substance or alloy (such as stainless steel, etc.) containing at least one element of C, Cu, Ni, Fe, V, Nb, Ti, Cr, Mo, Ru, Rh, Ta, W, Os, Ir, Pt, Au, and Ag can be used. It can also be a composite material formed by plating different conductive substances on a conductive substance, for example, Cu can be plated on Fe.

[0235] From the viewpoint of high conductivity, high stability in electrolyte and good oxidation resistance, Cu foil, Ni foil, stainless steel foil, etc. are optional. From the viewpoint of further reducing production cost, Cu foil and Ni foil are optional. Those skilled in the art can adjust according to actual conditions.

[0236] The negative electrode active material layer includes a negative electrode active material, which may include at least one of a carbon material and a silicon-based material.

[0237] The mass content of the silicon-based material in the negative electrode active material may be 0% to 25%. A mass content of the silicon-based material of 0% means that the negative electrode active material does not contain the silicon-based material.

[0238] As an example, the carbon material may include natural graphite, artificial graphite, or a mixture thereof.

[0239] As an example, the silicon-based material may include at least one of elemental silicon, silicon oxide, a silicon-carbon composite material, and a silicon alloy.

[0240] In some embodiments, the porosity of the negative active material layer may be 25% to 45%.

[0241] In some embodiments, the thickness of the negative electrode active material layer may be 30 μm to 150 μm, which is not limited in the present embodiment. The thickness of the negative electrode active material layer refers to the thickness of the negative electrode active material layer located on one side of the negative electrode current collector.

[0242] In some embodiments, the negative electrode active material layer may include a negative electrode conductive agent. The negative electrode conductive agent may include conductive carbon powder. As an example, the negative electrode conductive agent may include, but is not limited to, at least one of conductive carbon black, acetylene black (AB), Ketjen black (KB), graphite, carbon fiber, carbon tube, graphene, amorphous carbon, hard carbon, soft carbon, glassy carbon, carbon nanofiber, and carbon nanotube (CNT). These materials may be used alone or in combination of two or more.

[0243] In some embodiments, the negative electrode active material layer may include a negative electrode binder. The negative electrode binder may include, butadiene styrene rubber (SBR), acrylonitrile multipolymer (e.g., LA-type water-based binder, optionally LA132, LA133), polyacrylic acid (PAA) and its salt, styrene acrylic resin, polyvinyl alcohol (PVA), and at least one of their respective derivatives. Derivatives generally refer to products derived from the substitution of hydrogen atoms or atomic groups in a polymer by other atoms or atomic groups.

[0244] In some embodiments, the negative electrode active material layer may further include a negative electrode dispersant, thereby improving the film-forming quality of the negative electrode active material layer. As an example, the negative electrode dispersant may include, but is not limited to, at least one of sodium carboxymethyl cellulose (CMC) and its derivatives. Derivatives generally refer to products derived from the replacement of hydrogen atoms or atomic groups in a polymer by other atoms or atomic groups (such as amino groups, etc.).

[0245] The negative electrode sheet can be prepared according to conventional methods in the art. Usually, the negative electrode active material, negative electrode conductive agent, negative electrode binder, negative electrode dispersant, etc. are dispersed in a solvent to form a negative electrode slurry, and the negative electrode slurry is coated on the negative electrode current collector, and the negative electrode sheet is obtained through processes such as drying and compaction. The solvent may include but is not limited to at least one of water, ethanol, acetone, butanone, dimethylformamide, N-methylpyrrolidone, diethylformamide, dimethyl sulfoxide, and tetrahydrofuran.

[0246] The coating method may be a coating method known in the art, such as extrusion coating, gravure coating, micro-gravure coating, electrospraying, transfer coating, etc., which is not limited in the embodiments of the present application.

[0247] The negative electrode sheet provided in the embodiments of the present application does not exclude other additional functional layers in addition to the negative electrode active material layer. For example, in some embodiments, the negative electrode sheet may also include a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode active material layer and disposed on the surface of the negative electrode current collector; in some embodiments, the negative electrode sheet may also include a protective layer covering the surface of the negative electrode active material layer.

[0248] Electronic Devices

[0249] In a third aspect, the embodiments of the present application further provide an electronic device, which includes the electrochemical device of the second aspect of the embodiments of the present application.

[0250] The electronic device provided in the embodiments of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. In some embodiments, the electronic device can include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0251] Example

[0252] The following examples describe the disclosure of the present application in more detail, and these examples are only for illustrative purposes, as it is obvious to those skilled in the art that various modifications and variations can be made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment, and the instruments used in the examples are commercially available.

[0253] Test Section

[0254] (1) Particle size test

[0255] The average particle size of the first filler particles, the second microsphere filler particles, and the third polymer binder microsphere particles is tested as follows: use a scanning electron microscope to refer to JY / T010-1996, obtain the SEM image of the diaphragm, arbitrarily select a test sample with a length × width of 50mm × 100mm on the diaphragm, randomly select 5 test areas in the test sample, and read the particle size of each particle in each test area at a certain magnification (for example, more than 500 times); count the number of particles and particle size values ​​in each test area, and take the arithmetic mean of the particle size of all particles in each test area as the average particle size of the particles. In order to ensure the accuracy of the test results, 10 test samples can be taken for the above test, and the average value of each test sample is taken as the final test result. The test instrument is ZEISS Sigma300. It should be noted that when the particle is irregular in shape, the distance between the two farthest points on the particle is taken as the particle size of the particle.

[0256] The diameter of the cavity of the second microsphere filler particles and the third polymer binder microsphere particles refers to the straight-line distance passing through the center of the hollow cavity and extending to both ends of the hollow cavity, which can be measured by taking an average value at 50 positions in the diaphragm cross-section image.

[0257] The thickness of the shell of the second microsphere filler particles and the third polymer binder microsphere particles refers to the distance between the inner surface and the outer surface of the microsphere particles. The distance between the inner surface and the outer surface of the microsphere particles can be measured at 50 positions in the diaphragm section image and then the average value is taken.

[0258] (2) Thickness change rate test of porous coating

[0259] The thickness change rate of the porous coating at 85°C and 1Mpa pressure for 20s is tested as follows: the diaphragm is punched into a sample with a width of 50mm and a length of 100mm, and then two pieces of Teflon (PTFE) films of the same size are used to form a "sandwich" structure with the sample, and hot-pressed for 20s (seconds) in a hot press at 85°C and 1Mpa pressure, and finally the sample is separated from the Teflon film, and the thickness D2 of the porous coating of the diaphragm after hot pressing is tested. The thickness change rate of the porous coating at 85°C and 1Mpa pressure for 20s = (D1-D2) / D1*100%, where D1 is the thickness of the porous coating of the diaphragm before hot pressing.

[0260] The thickness of the porous coating refers to the distance between the surface of the third polymer binder microsphere particles (the second microsphere filler particles in Example 13) away from the porous substrate and the porous substrate. For accuracy, the distance between the surface of more than 10 particles away from the porous substrate and the porous substrate can be measured during the test, and then the average value is taken as the thickness of the porous coating.

[0261] (3) Adhesion test between porous coating of diaphragm and electrode plate

[0262] The diaphragm and the electrode sheet (such as the negative electrode sheet or the positive electrode sheet) are punched into samples with a width of 15 mm and a length of 20 cm to 30 cm, and then the porous coating of the diaphragm is aligned and bonded to the surface of the electrode sheet, and then hot-pressed for 60 seconds (seconds) in a hot press at 85°C and 1 MPa pressure. Finally, the hot-pressed diaphragm and electrode sheet complex is taken out, and a 180° peeling test is performed on a tensile testing machine to obtain the bonding strength, and the peeling speed is 50 mm / min.

[0263] (4) Cycle performance test of lithium-ion secondary batteries

[0264] The lithium-ion secondary battery was placed at 25°C for 60 minutes, then charged at a constant current of 0.5C to a full charge voltage of 4.25V, and then continued to be charged at a constant voltage of 4.25V to a cut-off current of 0.02C. After being placed at 5 minutes, it was discharged at a constant current of 0.5C to 3.0V. This was a charge and discharge cycle, and the discharge capacity of the first cycle was recorded. The lithium-ion secondary battery was cycled 1000 times according to the above steps, and the discharge capacity after 1000 cycles was recorded.

[0265] The capacity retention rate of the lithium ion secondary battery after 1000 cycles = (discharge capacity after 1000 cycles / first cycle discharge capacity) × 100%.

[0266] Example 1

[0267] (1) Preparation of diaphragm

[0268] The first filler particles, the second microsphere filler particles, the third polymer binder microsphere particles, and the polyacrylic acid binder are fully and evenly dispersed in deionized water at a solid content mass ratio of 75:10:10:5 to obtain a porous coating slurry; the porous coating slurry is evenly coated on a polyethylene porous substrate with a thickness of 5 μm, and then dried in an oven to obtain a separator. The thickness of the porous coating is 6 μm.

[0269] The first filler particles are boehmite, and the average particle size is 1 μm.

[0270] The second microsphere filler particle includes a cavity and a shell covering the cavity, the shell includes a plurality of pore structures, the shell includes a first shell layer and a second shell layer, the second shell layer is located between the first shell layer and the cavity of the second microsphere filler particle, the first shell layer is polystyrene, the second shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 38:62, the first shell layer and the second shell layer are connected by a CC covalent bond, the diameter of the cavity is 0.6 μm, the average thickness of the shell is 0.1 μm, and the average particle size of the second microsphere filler particles is 0.8 μm.

[0271] The third polymer binder microsphere particles include a cavity and a shell covering the cavity, the shell includes multiple pore structures, the shell includes a third shell layer and a fourth shell layer, the fourth shell layer is located between the third shell layer and the cavity of the third polymer binder microsphere particles, the third shell layer is polystyrene, the fourth shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 35:65, the third shell layer and the fourth shell layer are connected by a CC covalent bond, the diameter of the cavity is 3.2μm, the average thickness of the shell is 0.4μm, and the average particle size of the third polymer binder microsphere particles is 4μm.

[0272] (2) Preparation of negative electrode sheet

[0273] Artificial graphite, acetylene black, styrene-butadiene rubber, and sodium carboxymethyl cellulose were mixed at a solid content mass ratio of 96:1:1.5:1.5, and then deionized water was added as a solvent to prepare a slurry with a solid content of 70%, and stirred evenly. The slurry was evenly coated on one surface of a copper foil with a thickness of 8 μm, and dried and cold pressed at 110°C to obtain a single-sided coated negative electrode sheet with a negative electrode active material layer thickness of 150 μm. Then repeat the above steps on the other surface of the copper foil to obtain a double-sided coated negative electrode sheet. The negative electrode sheet was cut into a specification of 80 mm × 880 mm and welded to the pole ear for standby use.

[0274] (3) Preparation of positive electrode sheet

[0275] LiCoO2, acetylene black, and polyvinylidene fluoride (PVDF) were mixed at a solid content mass ratio of 94:3:3, and then N-methylpyrrolidone (NMP) was added as a solvent to prepare a slurry with a solid content of 75%, and stirred evenly. The slurry was evenly coated on one surface of an aluminum foil with a thickness of 12 μm, and dried and cold pressed at 90°C to obtain a single-sided coated positive electrode sheet with a positive electrode active material layer thickness of 100 μm. Then repeat the above steps on the other surface of the aluminum foil to obtain a double-sided coated positive electrode sheet. The positive electrode sheet was cut into a specification of 74 mm × 867 mm and welded to the pole ear for standby use.

[0276] (4) Preparation of electrolyte

[0277] In an environment with a water content of less than 10 ppm, ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), propyl propionate (PP), and vinylene carbonate (VC) are mixed in a mass ratio of 20:30:20:28:2, and then LiPF6 is added and mixed evenly to obtain an electrolyte. The mass fraction of LiPF6 in the electrolyte is 8%.

[0278] (5) Preparation of lithium-ion secondary batteries

[0279] The positive electrode sheet, separator and negative electrode sheet prepared above are stacked and wound in order to obtain an electrode assembly. The electrode assembly is placed in an aluminum-plastic film packaging bag, dehydrated at 80°C, injected with the prepared electrolyte, and subjected to vacuum packaging, standing, hot pressing, shaping and other processes to obtain a soft-pack lithium-ion secondary battery.

[0280] Example 2

[0281] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0282] The second microsphere filler particle includes a cavity and a shell covering the cavity, the shell includes a plurality of pore structures, the shell includes a first shell layer and a second shell layer, the second shell layer is located between the first shell layer and the cavity of the second microsphere filler particle, the first shell layer is polystyrene, the second shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 38:62, the first shell layer and the second shell layer are connected by a CC covalent bond, the diameter of the cavity is 0.1 μm, the average thickness of the shell is 0.05 μm, and the average particle size of the second microsphere filler particles is 0.2 μm.

[0283] Example 3

[0284] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0285] The second microsphere filler particle includes a cavity and a shell covering the cavity, the shell includes a plurality of pore structures, the shell includes a first shell layer and a second shell layer, the second shell layer is located between the first shell layer and the cavity of the second microsphere filler particle, the first shell layer is polystyrene, the second shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 38:62, the first shell layer and the second shell layer are connected by a CC covalent bond, the diameter of the cavity is 0.1 μm, the average thickness of the shell is 0.075 μm, and the average particle size of the second microsphere filler particles is 0.25 μm.

[0286] Example 4

[0287] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0288] The second microsphere filler particle includes a cavity and a shell covering the cavity, the shell includes a plurality of pore structures, the shell includes a first shell layer and a second shell layer, the second shell layer is located between the first shell layer and the cavity of the second microsphere filler particle, the first shell layer is polystyrene, the second shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 38:62, the first shell layer and the second shell layer are connected by a CC covalent bond, the diameter of the cavity is 0.1 μm, the average thickness of the shell is 0.1 μm, and the average particle size of the second microsphere filler particles is 0.3 μm.

[0289] Example 5

[0290] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0291] The second microsphere filler particle includes a cavity and a shell covering the cavity, the shell includes a plurality of pore structures, the shell includes a first shell layer and a second shell layer, the second shell layer is located between the first shell layer and the cavity of the second microsphere filler particle, the first shell layer is polystyrene, the second shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 38:62, the first shell layer and the second shell layer are connected by a CC covalent bond, the diameter of the cavity is 0.4 μm, the average thickness of the shell is 0.1 μm, and the average particle size of the second microsphere filler particles is 0.6 μm.

[0292] Example 6

[0293] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0294] The second microsphere filler particle includes a cavity and a shell covering the cavity, the shell includes a plurality of pore structures, the shell includes a first shell layer and a second shell layer, the second shell layer is located between the first shell layer and the cavity of the second microsphere filler particle, the first shell layer is polystyrene, the second shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 38:62, the first shell layer and the second shell layer are connected by a CC covalent bond, the diameter of the cavity is 0.8 μm, the average thickness of the shell is 0.1 μm, and the average particle size of the second microsphere filler particles is 1 μm.

[0295] Example 7

[0296] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0297] The second microsphere filler particle includes a cavity and a shell covering the cavity, the shell includes a plurality of pore structures, the shell includes a first shell layer and a second shell layer, the second shell layer is located between the first shell layer and the cavity of the second microsphere filler particle, the first shell layer is polystyrene, the second shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 38:62, the first shell layer and the second shell layer are connected by a CC covalent bond, the diameter of the cavity is 1.8 μm, the average thickness of the shell is 0.1 μm, and the average particle size of the second microsphere filler particles is 2 μm.

[0298] Example 8

[0299] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0300] The third polymer binder microsphere particles include a cavity and a shell covering the cavity, the shell includes multiple pore structures, the shell includes a third shell layer and a fourth shell layer, the fourth shell layer is located between the third shell layer and the cavity of the third polymer binder microsphere particles, the third shell layer is polystyrene, the fourth shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 35:65, the third shell layer and the fourth shell layer are connected by a CC covalent bond, the diameter of the cavity is 0.7μm, the average thickness of the shell is 0.4μm, and the average particle size of the third polymer binder microsphere particles is 1.5μm.

[0301] Example 9

[0302] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0303] The third polymer binder microsphere particles include a cavity and a shell covering the cavity, the shell includes multiple pore structures, the shell includes a third shell layer and a fourth shell layer, the fourth shell layer is located between the third shell layer and the cavity of the third polymer binder microsphere particles, the third shell layer is polystyrene, the fourth shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 35:65, the third shell layer and the fourth shell layer are connected by a CC covalent bond, the diameter of the cavity is 2.2μm, the average thickness of the shell is 0.4μm, and the average particle size of the third polymer binder microsphere particles is 3μm.

[0304] Example 10

[0305] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0306] The thickness of the porous coating layer was 10 μm.

[0307] The third polymer binder microsphere particles include a cavity and a shell covering the cavity, the shell includes multiple pore structures, the shell includes a third shell layer and a fourth shell layer, the fourth shell layer is located between the third shell layer and the cavity of the third polymer binder microsphere particles, the third shell layer is polystyrene, the fourth shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 35:65, the third shell layer and the fourth shell layer are connected by a CC covalent bond, the diameter of the cavity is 7.2μm, the average thickness of the shell is 0.4μm, and the average particle size of the third polymer binder microsphere particles is 8μm.

[0308] Embodiment 11

[0309] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0310] The thickness of the porous coating layer was 11 μm.

[0311] The third polymer binder microsphere particles include a cavity and a shell covering the cavity, the shell includes multiple pore structures, the shell includes a third shell layer and a fourth shell layer, the fourth shell layer is located between the third shell layer and the cavity of the third polymer binder microsphere particles, the third shell layer is polystyrene, the fourth shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 35:65, the third shell layer and the fourth shell layer are connected by a CC covalent bond, the diameter of the cavity is 8.2μm, the average thickness of the shell is 0.4μm, and the average particle size of the third polymer binder microsphere particles is 9μm.

[0312] Example 12

[0313] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0314] The thickness of the porous coating layer was 12 μm.

[0315] The third polymer binder microsphere particles include a cavity and a shell covering the cavity, the shell includes multiple pore structures, the shell includes a third shell layer and a fourth shell layer, the fourth shell layer is located between the third shell layer and the cavity of the third polymer binder microsphere particles, the third shell layer is polystyrene, the fourth shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate and methyl methacrylate is 35:65, the third shell layer and the fourth shell layer are connected by a CC covalent bond, the diameter of the cavity is 9.2μm, the average thickness of the shell is 0.4μm, and the average particle size of the third polymer binder microsphere particles is 10μm.

[0316] Example 13

[0317] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0318] The second microsphere filler particle includes a cavity and a shell covering the cavity, the shell includes a plurality of pore structures, the shell includes a first shell layer and a second shell layer, the second shell layer is located between the first shell layer and the cavity of the second microsphere filler particle, the first shell layer is polystyrene, the second shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 38:62, the first shell layer and the second shell layer are connected by a CC covalent bond, the diameter of the cavity is 1.8 μm, the average thickness of the shell is 0.1 μm, and the average particle size of the second microsphere filler particles is 2 μm.

[0319] The third polymer binder microsphere particles include a cavity and a shell covering the cavity, the shell includes multiple pore structures, the shell includes a third shell layer and a fourth shell layer, the fourth shell layer is located between the third shell layer and the cavity of the third polymer binder microsphere particles, the third shell layer is polystyrene, the fourth shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 35:65, the third shell layer and the fourth shell layer are connected by a CC covalent bond, the diameter of the cavity is 0.7μm, the average thickness of the shell is 0.4μm, and the average particle size of the third polymer binder microsphere particles is 1.5μm.

[0320] Comparative Example 1

[0321] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0322] (1) Preparation of diaphragm

[0323] Deionized water and boehmite particles are pre-dispersed, and then a polyacrylic acid binder is added and the mixture is stirred and mixed evenly. Then, a wetting agent, dimethylsiloxane, is added, stirred evenly, and degassed to obtain a porous coating slurry. The porous coating slurry is evenly coated on a polyethylene porous substrate with a thickness of 5 μm, and then dried in an oven to obtain a diaphragm.

[0324] The average particle size of boehmite is 1 μm. The solid content mass ratio of boehmite particles, binder, and wetting agent is 95:4:1. The thickness of the porous coating is 6 μm.

[0325] Comparative Example 2

[0326] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0327] (1) Preparation of diaphragm

[0328] The third polymer binder microsphere particles and the polyacrylic acid binder are fully and evenly dispersed in deionized water at a solid content mass ratio of 95:5 to obtain a porous coating slurry; the porous coating slurry is evenly coated on a polyethylene porous substrate with a thickness of 5 μm, and then dried in an oven to obtain a separator. The thickness of the porous coating is 6 μm.

[0329] The third polymer binder microsphere particles include a cavity and a shell covering the cavity, the shell includes multiple pore structures, the shell includes a third shell layer and a fourth shell layer, the fourth shell layer is located between the third shell layer and the cavity of the third polymer binder microsphere particles, the third shell layer is polystyrene, the fourth shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 35:65, the third shell layer and the fourth shell layer are connected by a CC covalent bond, the diameter of the cavity is 3.2μm, the average thickness of the shell is 0.4μm, and the average particle size of the third polymer binder microsphere particles is 4μm.

[0330] Comparative Example 3

[0331] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0332] (1) Preparation of diaphragm

[0333] The second microsphere filler particles and the polyacrylic acid binder were fully and evenly dispersed in deionized water at a solid content mass ratio of 95:5 to obtain a porous coating slurry; the porous coating slurry was evenly coated on a polyethylene porous substrate with a thickness of 5 μm, and then dried in an oven to obtain a separator. The thickness of the porous coating was 6 μm.

[0334] The second microsphere filler particle includes a cavity and a shell covering the cavity, the shell includes a plurality of pore structures, the shell includes a first shell layer and a second shell layer, the second shell layer is located between the first shell layer and the cavity of the second microsphere filler particle, the first shell layer is polystyrene, the second shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 38:62, the first shell layer and the second shell layer are connected by a CC covalent bond, the diameter of the cavity is 0.6 μm, the average thickness of the shell is 0.1 μm, and the average particle size of the second microsphere filler particles is 0.8 μm.

[0335] Comparative Examples 4 to 7

[0336] Except for the parameters adjusted according to Table 1, the remaining preparation processes of the lithium ion secondary battery are the same as those of Example 1.

[0337] Table 1

[0338]

[0339] From the test results of Examples 1 to 13 and Comparative Examples 1 to 7, it can be seen that the porous coating of the diaphragm in the present application includes first filler particles, second microsphere filler particles, and third polymer binder microsphere particles, and the average particle size of the second microsphere filler particles is 0.2μm to 2μm, and the average particle size of the third polymer binder microsphere particles is 1.5μm to 10μm. The diaphragm has high adhesion, good electrolyte wettability and good electrolyte retention, and the lithium-ion secondary battery using the diaphragm has good cycle performance.

[0340] The porous coating layer of the separator of Comparative Example 1 does not include the second microsphere filler particles and the third polymer binder microsphere particles, and the adhesion, electrolyte wettability and electrolyte retention of the separator are all poor, and the cycle performance of the lithium ion secondary battery is also poor.

[0341] The porous coating of the diaphragm of Comparative Example 2 and Comparative Example 3 only includes the third polymer binder microsphere particles or the second microsphere filler particles, the heat resistance of the diaphragm will deteriorate, and the mechanical strength of the diaphragm will also be reduced. It is easy to deform during the cyclic charge and discharge process of the lithium-ion secondary battery, thereby resulting in poor cycle performance of the lithium-ion secondary battery.

[0342] The average particle size of the second microsphere filler particles used in Comparative Example 4 is too small. When the dosage is the same, the number of the second microsphere filler particles increases, which will reduce the ion transport properties of the porous coating, thereby resulting in poor cycle performance of the lithium ion secondary battery.

[0343] The average particle size of the second microsphere filler particles used in Comparative Example 5 is too large. When the dosage is the same, the number of the second microsphere filler particles is small, and the improvement effect on the membrane electrolyte wettability and liquid retention is poor, thereby resulting in poor cycle performance of the lithium ion secondary battery.

[0344] The average particle size of the third polymer binder microsphere particles used in Comparative Example 6 is too small, and its buffering effect on the volume expansion of the electrode plate is poor, and the improvement effect on the interfacial electrolyte wettability at the corner is poor, which leads to poor cycle performance of the lithium-ion secondary battery.

[0345] The average particle size of the third polymer binder microsphere particles used in Comparative Example 7 is too large, which will cause the porous coating to have a large thickness change rate, and its extrusion resistance will deteriorate, and it will be easily deformed under the expansion force of the electrode plate, thereby resulting in a decrease in its own ability to store and retain electrolyte, and further resulting in poor cycle performance of the lithium-ion secondary battery.

[0346] By comparing Example 7 and Example 13, it can also be seen that when the average particle size of the third polymer binder microsphere particles is larger than the average particle size of the second microsphere filler particles, the diaphragm and the electrode plate can be better bonded, and a sufficient gap can be formed between the diaphragm and the electrode plate to buffer the volume expansion of the electrode plate, thereby better improving the electrolyte wettability at the corner interface, improving the problem of purple spot lithium precipitation at the corner interface, and effectively improving the cycle performance of the lithium-ion secondary battery.

[0347] It can also be seen from the above test results that further adjusting the average particle size of the second microsphere filler particles is beneficial to improving the cycle performance of the lithium-ion secondary battery.

[0348] It can also be seen from the above test results that further adjusting the average particle size of the third polymer binder microsphere particles is beneficial to improving the cycle performance of the lithium-ion secondary battery.

[0349] Example 1-1

[0350] The preparation process of the lithium ion secondary battery is the same as that of Example 1, except that the average particle size of boehmite in the preparation process of the separator is 0.2 μm.

[0351] Example 1-2

[0352] The preparation process of the lithium ion secondary battery is the same as that of Example 1, except that the average particle size of boehmite in the preparation process of the separator is 0.25 μm.

[0353] Examples 1-3

[0354] The preparation process of the lithium ion secondary battery is the same as that of Example 1, except that the average particle size of boehmite in the preparation process of the separator is 0.3 μm.

[0355] Examples 1-4

[0356] The preparation process of the lithium ion secondary battery is the same as that of Example 1, except that the average particle size of boehmite in the preparation process of the separator is 1.5 μm.

[0357] Examples 1-5

[0358] The preparation process of the lithium ion secondary battery is the same as that of Example 1, except that the average particle size of boehmite in the preparation process of the separator is 2 μm.

[0359] Examples 1-6

[0360] The preparation process of the lithium ion secondary battery is the same as that of Example 1, except that the average particle size of boehmite in the preparation process of the separator is 0.1 μm.

[0361] Examples 1-7

[0362] The preparation process of the lithium ion secondary battery is the same as that of Example 1, except that the average particle size of boehmite in the preparation process of the separator is 2.2 μm.

[0363] Table 2

[0364] Serial number Average particle size of the first filler particles (μm) Porous coating thickness (μm) Capacity retention after 1000 cycles Example 1-1 0.2 6 76.6% Example 1-2 0.25 6 76.8% Examples 1-3 0.3 6 80.4% Example 1 1 6 81.5% Examples 1-4 1.5 6 78.8% Examples 1-5 2 6 78.5% Examples 1-6 0.1 6 75.0% Examples 1-7 2.2 6 75.2%

[0365] It can be seen from the above test results that further adjusting the average particle size of the first filler particles is beneficial for the lithium-ion secondary battery to have a further improved cycle performance on the basis of high energy density.

[0366] Example 2-1

[0367] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0368] The second microsphere filler particle includes a cavity and a shell covering the cavity, the shell includes a plurality of pore structures, the shell includes a first shell layer and a second shell layer, the second shell layer is located between the first shell layer and the cavity of the second microsphere filler particle, the first shell layer is polystyrene, the second shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 38:62, the first shell layer and the second shell layer are connected by a CC covalent bond, the diameter of the cavity is 0.7 μm, the average thickness of the shell is 0.05 μm, and the average particle size of the second microsphere filler particles is 0.8 μm.

[0369] Example 2-2

[0370] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0371] The second microsphere filler particle includes a cavity and a shell covering the cavity, the shell includes a plurality of pore structures, the shell includes a first shell layer and a second shell layer, the second shell layer is located between the first shell layer and the cavity of the second microsphere filler particle, the first shell layer is polystyrene, the second shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 38:62, the first shell layer and the second shell layer are connected by a CC covalent bond, the diameter of the cavity is 0.64 μm, the average thickness of the shell is 0.08 μm, and the average particle size of the second microsphere filler particles is 0.8 μm.

[0372] Example 2-3

[0373] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0374] The second microsphere filler particle includes a cavity and a shell covering the cavity, the shell includes multiple pore structures, the shell includes a first shell layer and a second shell layer, the second shell layer is located between the first shell layer and the cavity of the second microsphere filler particle, the first shell layer is polystyrene, the second shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 38:62, the first shell layer and the second shell layer are connected by a CC covalent bond, the diameter of the cavity is 0.56μm, the average thickness of the shell is 0.12μm, and the average particle size of the second microsphere filler particles is 0.8μm.

[0375] Embodiment 2-4

[0376] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0377] The second microsphere filler particle includes a cavity and a shell covering the cavity, the shell includes multiple pore structures, the shell includes a first shell layer and a second shell layer, the second shell layer is located between the first shell layer and the cavity of the second microsphere filler particle, the first shell layer is polystyrene, the second shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 38:62, the first shell layer and the second shell layer are connected by a CC covalent bond, the diameter of the cavity is 0.4μm, the average thickness of the shell is 0.2μm, and the average particle size of the second microsphere filler particles is 0.8μm.

[0378] Table 3

[0379]

[0380] It can be seen from the above test results that further adjusting the average thickness of the shell of the second microsphere filler particles is beneficial to improving the cycle performance of the lithium-ion secondary battery.

[0381] Example 3-1

[0382] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0383] The third polymer binder microsphere particles include a cavity and a shell covering the cavity, the shell includes multiple pore structures, the shell includes a third shell layer and a fourth shell layer, the fourth shell layer is located between the third shell layer and the cavity of the third polymer binder microsphere particles, the third shell layer is polystyrene, the fourth shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate and methyl methacrylate is 35:65, the third shell layer and the fourth shell layer are connected by a CC covalent bond, the diameter of the cavity is 3.4μm, the average thickness of the shell is 0.3μm, and the average particle size of the third polymer binder microsphere particles is 4μm.

[0384] Example 3-2

[0385] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0386] The third polymer binder microsphere particles include a cavity and a shell covering the cavity, the shell includes multiple pore structures, the shell includes a third shell layer and a fourth shell layer, the fourth shell layer is located between the third shell layer and the cavity of the third polymer binder microsphere particles, the third shell layer is polystyrene, the fourth shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate and methyl methacrylate is 35:65, the third shell layer and the fourth shell layer are connected by a CC covalent bond, the diameter of the cavity is 2.8μm, the average thickness of the shell is 0.6μm, and the average particle size of the third polymer binder microsphere particles is 4μm.

[0387] Example 3-3

[0388] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0389] The third polymer binder microsphere particles include a cavity and a shell covering the cavity, the shell includes multiple pore structures, the shell includes a third shell layer and a fourth shell layer, the fourth shell layer is located between the third shell layer and the cavity of the third polymer binder microsphere particles, the third shell layer is polystyrene, the fourth shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 35:65, the third shell layer and the fourth shell layer are connected by a CC covalent bond, the diameter of the cavity is 2μm, the average thickness of the shell is 1μm, and the average particle size of the third polymer binder microsphere particles is 4μm.

[0390] Table 4

[0391]

[0392] It can be seen from the above test results that further adjusting the average thickness of the shell of the third polymer binder microsphere particles is beneficial to improving the cycle performance of the lithium-ion secondary battery.

[0393] Example 4-1

[0394] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0395] The solid content mass ratio of the first filler particles, the second microsphere filler particles, the third polymer binder microsphere particles, and the polyacrylic acid binder is 70:15:10:5.

[0396] Example 4-2

[0397] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0398] The solid content mass ratio of the first filler particles, the second microsphere filler particles, the third polymer binder microsphere particles, and the polyacrylic acid binder is 80:5:10:5.

[0399] Example 4-3

[0400] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0401] The solid content mass ratio of the first filler particles, the second microsphere filler particles, the third polymer binder microsphere particles, and the polyacrylic acid binder is 84:1:10:5.

[0402] Example 4-4

[0403] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0404] The solid content mass ratio of the first filler particles, the second microsphere filler particles, the third polymer binder microsphere particles, and the polyacrylic acid binder is 75:5:15:5.

[0405] The thickness of the porous coating layer of the separator was 10 μm.

[0406] Embodiment 4-5

[0407] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0408] The solid content mass ratio of the first filler particles, the second microsphere filler particles, the third polymer binder microsphere particles, and the polyacrylic acid binder is 75:8:12:5.

[0409] The thickness of the porous coating layer of the separator was 8 μm.

[0410] Embodiment 4-6

[0411] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0412] The solid content mass ratio of the first filler particles, the second microsphere filler particles, the third polymer binder microsphere particles, and the polyacrylic acid binder is 75:12:8:5.

[0413] Table 5

[0414]

[0415] It can be seen from the above test results that further adjusting the mass proportion of the first filler particles, the second microsphere filler particles, and the third polymer binder microsphere particles is beneficial to fully exerting the high heat resistance of the first filler particles, and is beneficial to maintaining the hollow structure of the second microsphere filler particles, so that the second microsphere filler particles can better play the role of storing and retaining electrolyte, and is also beneficial to fully exerting the role of the third polymer binder microsphere particles in improving the adhesion between the diaphragm and the electrode pole piece and buffering the volume expansion of the electrode pole piece, which is beneficial to improving the cycle performance of lithium-ion secondary batteries.

[0416] Example 5-1

[0417] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0418] The second microsphere filler particle includes a cavity and a shell covering the cavity, the shell includes a plurality of pore structures, the shell includes a first shell layer and a second shell layer, the second shell layer is located between the first shell layer and the cavity of the second microsphere filler particle, the first shell layer is polystyrene, the second shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 20:80, the first shell layer and the second shell layer are connected by a CC covalent bond, the diameter of the cavity is 0.6 μm, the average thickness of the shell is 0.1 μm, and the average particle size of the second microsphere filler particles is 0.8 μm.

[0419] Example 5-2

[0420] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0421] The second microsphere filler particle includes a cavity and a shell covering the cavity, the shell includes a plurality of pore structures, the shell includes a first shell layer and a second shell layer, the second shell layer is located between the first shell layer and the cavity of the second microsphere filler particle, the first shell layer is polystyrene, the second shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 40:60, the first shell layer and the second shell layer are connected by a CC covalent bond, the diameter of the cavity is 0.6 μm, the average thickness of the shell is 0.1 μm, and the average particle size of the second microsphere filler particles is 0.8 μm.

[0422] Table 6

[0423]

[0424] It can be seen from the above test results that further adjusting the ratio of the soft monomer structural unit to the hard monomer structural unit in the second shell layer of the second microsphere filler particles is beneficial to improving the cycle performance of the lithium ion secondary battery.

[0425] Example 6-1

[0426] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0427] The third polymer binder microsphere particles include a cavity and a shell covering the cavity, the shell includes multiple pore structures, the shell includes a third shell layer and a fourth shell layer, the fourth shell layer is located between the third shell layer and the cavity of the third polymer binder microsphere particles, the third shell layer is polystyrene, the fourth shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 40:60, the third shell layer and the fourth shell layer are connected by a CC covalent bond, the diameter of the cavity is 3.2μm, the average thickness of the shell is 0.4μm, and the average particle size of the third polymer binder microsphere particles is 4μm.

[0428] Example 6-2

[0429] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0430] The third polymer binder microsphere particles include a cavity and a shell covering the cavity, the shell includes multiple pore structures, the shell includes a third shell layer and a fourth shell layer, the fourth shell layer is located between the third shell layer and the cavity of the third polymer binder microsphere particles, the third shell layer is polystyrene, the fourth shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 23:77, the third shell layer and the fourth shell layer are connected by a CC covalent bond, the diameter of the cavity is 3.2μm, the average thickness of the shell is 0.4μm, and the average particle size of the third polymer binder microsphere particles is 4μm.

[0431] Table 7

[0432]

[0433] It can be seen from the above test results that further adjusting the ratio of the soft monomer structural unit and the hard monomer structural unit in the fourth shell layer of the third polymer binder microsphere particles is beneficial to improving the cycle performance of the lithium ion secondary battery.

[0434] Example 7-1

[0435] The preparation process of the lithium ion secondary battery is the same as that of Example 1 except for the following differences.

[0436] (1) Preparation of diaphragm

[0437] The first filler particles, the second microsphere filler particles, and the polyacrylic acid binder are fully and evenly dispersed in deionized water to obtain a first slurry; the third polymer binder microsphere particles and the polyacrylic acid binder are fully and evenly dispersed in deionized water to obtain a second slurry; the first slurry is evenly coated on a polyethylene porous substrate with a thickness of 5 μm, and then the second slurry is sprayed after drying in an oven, and then the diaphragm is obtained by drying in an oven. The thickness of the porous coating is 8 μm. The solid content mass ratio of the first filler particles, the second microsphere filler particles, the third polymer binder microsphere particles, and the polyacrylic acid binder in the porous coating is 75:10:10:5.

[0438] The first filler particles are boehmite, and the average particle size is 1 μm.

[0439] The second microsphere filler particle includes a cavity and a shell covering the cavity, the shell includes a plurality of pore structures, the shell includes a first shell layer and a second shell layer, the second shell layer is located between the first shell layer and the cavity of the second microsphere filler particle, the first shell layer is polystyrene, the second shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 38:62, the first shell layer and the second shell layer are connected by a CC covalent bond, the diameter of the cavity is 0.6 μm, the average thickness of the shell is 0.1 μm, and the average particle size of the second microsphere filler particles is 0.8 μm.

[0440] The third polymer binder microsphere particles include a cavity and a shell covering the cavity, the shell includes multiple pore structures, the shell includes a third shell layer and a fourth shell layer, the fourth shell layer is located between the third shell layer and the cavity of the third polymer binder microsphere particles, the third shell layer is polystyrene, the fourth shell layer is n-pentyl acrylate-methyl methacrylate copolymer, the mass ratio of n-pentyl acrylate to methyl methacrylate is 35:65, the third shell layer and the fourth shell layer are connected by a CC covalent bond, the diameter of the cavity is 3.2μm, the average thickness of the shell is 0.4μm, and the average particle size of the third polymer binder microsphere particles is 4μm.

[0441] Table 8

[0442]

[0443] The positions of the third polymer binder microsphere particles are different, and the effects of improving the cycle performance of lithium-ion secondary batteries are different.

[0444] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. A membrane comprising a porous substrate and a porous coating disposed on at least one side of the porous substrate, characterized in that: The porous coating comprises first filler particles, second microsphere filler particles, third polymer binder microsphere particles and a binder; The second microsphere filler particle comprises a cavity and a shell covering the cavity, the shell of the second microsphere filler particle comprises a plurality of pore structures, and the average particle size of the second microsphere filler particle is 0.2 μm to 2 μm; The third polymer binder microsphere particles include a cavity and a shell covering the cavity, the shell of the third polymer binder microsphere particles includes a plurality of pore structures, and the average particle size of the third polymer binder microsphere particles is 1.5 μm to 10 μm.

2. The diaphragm according to claim 1, characterized in that The diaphragm satisfies at least one of the following conditions (1) to (2): (1) The average particle size of the second microsphere filler particles is 0.3 μm to 2 μm; (2) The average particle size of the third polymer binder microsphere particles is 3 μm to 8 μm.

3. The diaphragm according to claim 1, characterized in that The average particle size of the third polymer binder microsphere particles is greater than the average particle size of the second microsphere filler particles.

4. The diaphragm according to claim 1, characterized in that The average particle size of the first filler particles is 0.2 μm to 2 μm.

5. The diaphragm according to claim 4, characterized in that The average particle size of the first filler particles is 0.3 μm to 1 μm.

6. The diaphragm according to claim 1, characterized in that The third polymer binder microsphere particles are embedded in the pores formed by the accumulation of the first filler particles and the second microsphere filler particles and form protrusions on the surface of the porous coating layer.

7. The diaphragm according to claim 1, characterized in that The porous coating layer includes a heat-resistant layer and an adhesive layer, wherein the heat-resistant layer is arranged on at least one side of the porous substrate, and the adhesive layer is arranged on at least a portion of the surface of the heat-resistant layer. The heat-resistant layer includes first filler particles, second microsphere filler particles and a binder, and the adhesive layer includes third polymer binder microsphere particles and a binder.

8. The diaphragm according to claim 1, characterized in that Taking the total mass of the porous coating as 100%, The mass fraction of the first filler particles is 70% to 84%, The mass fraction of the second microsphere filler particles is 1% to 15%, The mass fraction of the third polymer binder microsphere particles is 8% to 15%, The mass fraction of the binder is 1% to 5%.

9. The diaphragm according to claim 8, characterized in that Taking the total mass of the porous coating as 100%, The mass fraction of the first filler particles is 70% to 80%, The mass fraction of the second microsphere filler particles is 5% to 15%, The mass fraction of the third polymer binder microsphere particles is 8% to 12%, The mass fraction of the binder is 1% to 5%.

10. The diaphragm according to claim 1, characterized in that The thickness variation rate of the porous coating layer during hot pressing for 20 seconds at 85° C. and 1 MPa pressure is 10% to 80%.

11. The diaphragm according to claim 1, characterized in that The second microsphere filler particles satisfy at least one of the following conditions (1) to (4): (1) The average thickness of the shell of the second microsphere filler particle is 50 nm to 200 nm; (2) the diameter of the cavity of the second microsphere filler particle is 0.1 μm to 1.8 μm; (3) The specific surface area of ​​the second microsphere filler particles is 5 m 2 / g to 30m 2 / g; (4) The average pore size of the pore structure of the shell of the second microsphere filler particle is less than 10 nm.

12. The diaphragm according to claim 1, characterized in that The third polymer binder microsphere particles satisfy at least one of the following conditions (1) to (5): (1) The average thickness of the shell of the third polymer binder microsphere particles is 0.3 μm to 1 μm; (2) the diameter of the cavity of the third polymer binder microsphere particle is 0.7 μm to 9.2 μm; (3) The specific surface area of ​​the third polymer binder microsphere particles is 4 m 2 / g to 20m 2 / g; (4) the average pore size of the pore structure of the shell of the third polymer binder microsphere particles is less than 10 nm; (5) The glass transition temperature T of the third polymer binder microsphere particles g 60℃ to 100℃.

13. The diaphragm according to claim 1, characterized in that The shell of the second microsphere filler particle comprises a first shell layer and a second shell layer, the second shell layer is located between the first shell layer and the cavity of the second microsphere filler particle, the first shell layer comprises polystyrene, the second shell layer comprises an acrylic polymer, and the first shell layer and the second shell layer are connected by a CC covalent bond; The shell of the third polymer binder microsphere particle includes a third shell layer and a fourth shell layer, the fourth shell layer is located between the third shell layer and the cavity of the third polymer binder microsphere particle, the third shell layer includes polystyrene, the fourth shell layer includes an acrylic polymer, and the third shell layer and the fourth shell layer are connected by a CC covalent bond.

14. The diaphragm according to claim 1, characterized in that The diaphragm satisfies at least one of the following conditions (1) to (5): (1) The first filler particles include at least one of boehmite, aluminum oxide, zirconium oxide, titanium dioxide, magnesium oxide, silicon oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, yttrium oxide, mullite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, barium sulfate, silicon carbide, silicon nitride, boron nitride, aluminum nitride, melamine, and dicyandiamide; (2) The first filler particles are solid structures; (3) The specific surface area of ​​the first filler particles is less than or equal to 20 m 2 / g; (4) The glass transition temperature T of the binder g -40℃ to 15℃; (5) The adhesive comprises at least one of polymethacrylate adhesive, styrene-butadiene rubber, polyacrylic acid, and polyacrylate.

15. The diaphragm according to claim 1, characterized in that The diaphragm satisfies at least one of the following conditions (1) to (4): (1) The thickness of the porous substrate is 2 μm to 7 μm; (2) The thickness of the porous coating layer is 4 μm to 12 μm; (3) The total thickness of the diaphragm is 6 μm to 19 μm; (4) The bonding force between the porous substrate and the porous coating layer is 30 N / m to 100 N / m.

16. An electrochemical device, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and a separator according to any one of claims 1 to 15, wherein the separator is located between the positive electrode sheet and the negative electrode sheet.

17. The electrochemical device according to claim 16, characterized in that The bonding strength between the porous coating and the negative electrode plate in a hot pressing test at 85° C. and 1 MPa for 60 seconds is 5 N / m to 15 N / m; and / or, The bonding strength between the porous coating and the positive electrode plate is 5 N / m to 20 N / m when hot-pressed for 60 seconds at 85° C. and 1 MPa.

18. An electronic device, characterized in that: Comprising the electrochemical device according to claim 16 or 17.